Particles, molded body, and method for producing molded body
By reducing fluorescent luminescent coloring substances in methacrylic resins and introducing N-substituted maleimide monomer structural units and carrying out specific process processing, the problem of color tone reduction of optical components at high temperatures is solved, and the orientation is achieved Reduction of birefringence and photoelastic birefringence and improvement of hue and fluorescence intensity.
Patent Information
- Application Number
- CN202411075934.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-11-20
- Filing Date
- 2024-08-07
- Publication Date
- 2025-02-18
AI Technical Summary
Existing optical component materials are prone to color reduction in high temperature environments, and it is difficult to reduce orientation birefringence and photoelastic birefringence at the same time.
By reducing the content of the fluorescent luminescent coloring substance in the methacrylic resin and containing structural units from the N-substituted maleimide monomer in the main chain, specific processes such as light and heating treatment are used, A resin material with improved hue and fluorescence intensity was prepared.
It achieves the improvement of color tone stability and fluorescence intensity in high temperature environments, while reducing orientation birefringence and photoelastic birefringence, which is suitable for optical components under high temperature conditions.
Smart Images

Figure CN119463010A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to granules, shaped bodies and a method for producing the shaped bodies. Background Art
[0002] In the past, optical components such as lenses and prisms were made of glass, but in recent years, plastics have been used to achieve greater freedom in design, such as light weight and miniaturization or aspheric lenses. As plastics used for optical components, methacrylic resins, styrene resins, polycarbonates, cyclic olefin resins, etc. are generally known.
[0003] Generally, plastics are prone to birefringence due to orientation during molding, which can have a negative impact on imaging performance when used as optical components. Furthermore, when injection molding with high productivity is used as a molding method, it is easy to apply a greater orientation, which has a significant impact on imaging performance. Methacrylic resins represented by polymethyl methacrylate have high transparency and low inherent birefringence, so they can make the oriented birefringence lower and are suitable for use as optical components. However, since higher optical performance is required, a material that can further reduce the oriented birefringence is needed.
[0004] For example, Patent Documents 1 and 2 disclose that copolymers obtained by copolymerizing monomers containing methyl methacrylate, 2,2,2-trifluoroethyl methacrylate, and benzyl methacrylate can reduce orientation birefringence and photoelastic birefringence. This is based on the following concept: when making a homopolymer, multiple monomers with different signs of intrinsic birefringence and photoelastic coefficient are selected, combined and copolymerized, and the composition is adjusted to reduce the orientation birefringence and photoelastic birefringence of the copolymer. However, since the glass transition temperature of the copolymer is low, there is a problem that the use of the copolymer in electronic equipment or automobiles, which may become high temperature inside, is limited. Furthermore, the problem of color tone and the problem caused by further reduction of color tone when used in a high temperature environment cannot be solved.
[0005] Therefore, as injection molding resins with improved orientation birefringence and heat resistance, copolymers obtained by hydrogenating aromatic double bonds of copolymers obtained by polymerizing a monomer composition containing a (meth)acrylate monomer and an aromatic vinyl monomer (Patent Document 3) and (meth)acrylic resins having a glutarimide unit with a ring structure in the main chain (Patent Document 4) have been proposed. However, although these resins have low orientation birefringence, the photoelastic coefficient is not sufficiently reduced, and therefore there is a disadvantage that birefringence is generated due to residual strain during molding and stress generated when the optical component is fixed to the device.
[0006] Therefore, a non-birefringent resin material composed of a composition containing a resin such as a glutarimide acrylic resin and a graft copolymer (Patent Document 5), a methacrylic copolymer having a ring structure in the main chain obtained from a monomer containing a methacrylate monomer and two or more N-substituted maleimide monomers (Patent Document 6), and other resin materials having high heat resistance and reducing both orientation birefringence and photoelasticity in injection molded sheets have been proposed. However, the thicker the molded body of the composition containing multiple resins that are not completely compatible, the higher the haze and the worse the transparency, so the application as an optical component is limited. Although the methacrylic resin of Patent Document 6 also has low orientation birefringence and photoelastic coefficient as an injection molded body, it has the problem of reduced color tone caused by N-substituted maleimide, and in the case of a complex molded body with a variable thickness such as a lens or prism or a thin-walled molded body such as a light guide plate, it is necessary to perform high-temperature molding for the purpose of improving fluidity, which further causes problems such as reduced color tone. Therefore, a resin composition which reduces both the orientation birefringence and the photoelasticity and has excellent heat resistance and higher transparency is desired as a substitute for glass.
[0007] In addition, in the reduction of the hue of the methacrylic resin containing a structural unit having a ring structure in the main chain, for example, regarding the reduction of the hue caused by N-substituted maleimide, it is also reported that fluorescent coloring components are one of the main causes. For example, in Patent Document 7, there is a description that N-substituted maleimide or impurities of N-substituted maleimide are heated to 300° C. or above or provided to a devolatilization device with shearing, thereby modifying it into a coloring substance with fluorescent luminescence, causing the hue to be reduced, but there is a problem that the technology for reducing the substance causing coloration is not sufficient.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent Application Publication No. 2006-308682.
[0011] Patent document 2: International Publication No. 2015 / 098980.
[0012] Patent Document 3: Japanese Patent Application Publication No. 2008-15199.
[0013] Patent document 4: Japanese Patent Application Publication No. 2006-328330.
[0014] Patent document 5: International Publication No. 2015 / 098775.
[0015] Patent document 6: International Publication No. 2011 / 149088.
[0016] Patent document 7: Japanese Patent Application Publication No. 2020-63436. Summary of the invention
[0017] An object of the present invention is to provide particles comprising a methacrylic resin composition containing a methacrylic resin having a structural unit derived from an N-substituted maleimide monomer in the main chain, a molded article, and a method for producing the molded article, which have improved color tone and fluorescence intensity.
[0018] The present inventors have conducted intensive studies to solve the above-mentioned problems of the prior art, and as a result, have found that the above-mentioned problems can be solved by reducing the amount of fluorescent coloring matter contained in particles composed of a methacrylic resin composition containing a methacrylic resin containing a structural unit derived from an N-substituted maleimide monomer in the main chain.
[0019] That is, the present invention is as follows.
[0020] [1] A particle characterized in that the particle is composed of a methacrylic resin composition containing a methacrylic resin, the methacrylic resin contains a structural unit (X) derived from an N-substituted maleimide monomer in the main chain, and the particle contains less than 0.30 mass ppm of 2-amino-N-substituted maleimide.
[0021] [2] The particles according to [1], wherein the reflectance tint YI of the particles is 10 or less.
[0022] [3] The particles according to [1] or [2], wherein the average transmittance of light having a wavelength of 400 nm to 450 nm measured using a cuvette with an optical path length of 10 cm for a 20 w / v % chloroform solution of the particles is 90% or more.
[0023] [4] The particle according to any one of [1] to [3], wherein the fluorescence quantum yield of the fine powder of the particle when excited by light of 400 nm wavelength with a half-value width of 5 nm is 0.010 or less.
[0024] [5] The particles as described in any one of [1] to [4], wherein the content of 2-amino-N-substituted maleimide in the particles relative to the structural unit (X) derived from the N-substituted maleimide monomer of the methacrylic resin (amount of 2-amino-N-substituted maleimide / amount of structural unit (X) derived from the N-substituted maleimide monomer) is less than 1.5 mass ppm.
[0025] [6] The particles described in any one of [1] to [5], wherein the methacrylic resin composition is set to 100% by mass, the methacrylic resin composition contains 50% by mass or more of a methacrylic resin, and the methacrylic resin contains a structural unit (X) derived from an N-substituted maleimide monomer in the main chain.
[0026] [7] The particles according to any one of [1] to [6], wherein the methacrylic resin contains 3% by mass or more of a structural unit (X) derived from an N-substituted maleimide monomer in a main chain, assuming that the methacrylic resin accounts for 100% by mass.
[0027] [8] A molded product, characterized in that the molded product is obtained by molding the pellets according to any one of [1] to [7].
[0028] [9] A method for producing a molded article, which is a method for producing a molded article containing a methacrylic resin composition, characterized in that the method comprises: a step of polymerizing a methacrylic acid ester monomer, an N-substituted maleimide monomer, and optionally other vinyl monomers copolymerizable with the methacrylic acid ester monomer to obtain a methacrylic acid resin, and optionally adding an additive to obtain a methacrylic acid resin composition; a step of forming the methacrylic acid resin composition into particles; and a step of irradiating the particles with a wavelength of 360 to 460 nm and a cumulative light intensity of 0.1 W·hr / cm 2 ~10000W·hr / cm 2 the step of heating and melting the particles irradiated with the light to obtain a melt; and the step of injection molding the melt to obtain a molded body.
[0029] Effects of the Invention
[0030] According to the present invention, particles composed of a methacrylic resin composition containing a methacrylic resin containing a structural unit derived from an N-substituted maleimide monomer in the main chain, a molded article, and a method for producing a molded article having improved color tone and fluorescence intensity can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a schematic diagram of a long strip-shaped molded sheet used in Examples and Comparative Examples. DETAILED DESCRIPTION
[0032] Hereinafter, a mode for carrying out the present invention (hereinafter referred to as “the present embodiment”) will be described in detail, but the present invention is not limited to the following description and can be carried out with various modifications within the scope of the gist thereof.
[0033] (Methacrylic resin)
[0034] The methacrylic resin of the present embodiment is a methacrylic resin containing a structural unit derived from a methacrylic ester monomer and a structural unit (X) derived from an N-substituted maleimide monomer in the main chain, and optionally also containing other vinyl monomer units (Y) copolymerizable with the methacrylic ester monomer.
[0035] Hereinafter, each monomer structural unit will be described.
[0036] -Structural unit derived from methacrylate monomer-
[0037] First, the structural unit derived from the methacrylate monomer will be described.
[0038] The structural unit derived from the methacrylic acid ester monomer is formed from, for example, a monomer selected from the methacrylic acid esters shown below.
[0039] Examples of the methacrylate include methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, 2-ethylhexyl methacrylate, cyclopentyl methacrylate, cyclohexyl methacrylate, cyclooctyl methacrylate, tricyclodecyl methacrylate, dicyclooctyl methacrylate, tricyclododecyl methacrylate, isobornyl methacrylate, phenyl methacrylate, benzyl methacrylate, 1-phenylethyl methacrylate, 2-phenoxyethyl methacrylate, 3-phenylpropyl methacrylate, and 2,4,6-tribromophenyl methacrylate.
[0040] These monomers may be used alone or in combination of two or more.
[0041] Among the above methacrylates, methyl methacrylate and benzyl methacrylate are preferred from the viewpoint that the resulting methacrylic resin is excellent in transparency and weather resistance.
[0042] The structural unit derived from the methacrylate monomer may contain only one kind or two or more kinds.
[0043] The content of the structural unit derived from the methacrylate monomer is preferably 50 to 97% by mass, more preferably 55 to 97% by mass, further preferably 55 to 95% by mass, further preferably 60 to 93% by mass, and particularly preferably 60 to 90% by mass, based on 100% by mass of the methacrylic resin, from the viewpoint of sufficiently imparting heat resistance to the methacrylic resin by the structural unit (X) derived from the N-substituted maleimide monomer contained in the main chain described later.
[0044] It should be noted that the content of the structural unit derived from the methacrylate monomer can be determined by 1 H-NMR determination and 13 It can be determined by C-NMR measurement. 1 H-NMR determination and 13 C-NMR measurement can be performed at a measurement temperature of 40° C. using, for example, CDCl 3 or DMSO-d 6 as a measurement solvent.
[0045] The structural unit (X) derived from the N-substituted maleimide monomer contained in the main chain will be described below.
[0046] -Structural unit (X) derived from N-substituted maleimide monomer-
[0047] The structural unit (X) derived from the N-substituted maleimide monomer may be at least one selected from the monomer represented by the following formula (1) and / or the monomer represented by the following formula (2), and is preferably formed from both the monomers represented by the following formula (1) and the following formula (2).
[0048] Chemical formula 1
[0049]
[0050] In formula (1), R 1 represents any one of an arylalkyl group having 7 to 14 carbon atoms and an aryl group having 6 to 14 carbon atoms, and R 2 and R 3 Each independently represents any one of a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, an aryl group having 6 to 14 carbon atoms, and an amino group.
[0051] In addition, in R 2 In the case of an aryl group, R 2 It may contain halogen as a substituent.
[0052] In addition, R 1 It may be substituted with a substituent such as a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, a nitro group, or a benzyl group.
[0053] Chemical formula 2
[0054]
[0055] In formula (2), R 4 represents any one of a hydrogen atom, a cycloalkyl group having 3 to 12 carbon atoms, and an alkyl group having 1 to 12 carbon atoms, and R 5 and R 6 Each independently represents any one of a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, an aryl group having 6 to 14 carbon atoms, and an amino group.
[0056] A specific example is shown below.
[0057] Examples of the monomer represented by formula (1) include N-phenylmaleimide, N-benzylmaleimide, N-(2-chlorophenyl)maleimide, N-(4-chlorophenyl)maleimide, N-(4-bromophenyl)maleimide, N-(2-methylphenyl)maleimide, N-(2-ethylphenyl)maleimide, N-(2-methoxyphenyl)maleimide, N-(2-nitrophenyl)maleimide, N-(2,4,6-trimethylphenyl)maleimide, amine, N-(4-benzylphenyl)maleimide, N-(2,4,6-tribromophenyl)maleimide, N-naphthylmaleimide, N-anthrylmaleimide, 3-methyl-1-phenyl-1H-pyrrole-2,5-dione, 3,4-dimethyl-1-phenyl-1H-pyrrole-2,5-dione, 1,3-diphenyl-1H-pyrrole-2,5-dione, 1,3,4-triphenyl-1H-pyrrole-2,5-dione, 2-anilino-N-phenylmaleimide and the like.
[0058] Among these monomers, N-phenylmaleimide and N-benzylmaleimide are preferred from the viewpoint of excellent optics such as heat resistance and birefringence of the obtained methacrylic resin, and N-phenylmaleimide is particularly preferred from the viewpoint of heat resistance. The details of using N-phenylmaleimide as a monomer will be described later.
[0059] These monomers may be used alone or in combination of two or more.
[0060] Examples of the monomer represented by formula (2) include N-methylmaleimide, N-ethylmaleimide, N-n-propylmaleimide, N-isopropylmaleimide, N-n-butylmaleimide, N-isobutylmaleimide, N-sec-butylmaleimide, N-tert-butylmaleimide, N-n-pentylmaleimide, N-n-hexylmaleimide, N-n-heptylmaleimide, N-n-octylmaleimide, N-laurylmaleimide, N- Stearylmaleimide, N-cyclopentylmaleimide, N-cyclohexylmaleimide, 1-cyclohexyl-3-methyl-1-phenyl-1H-pyrrole-2,5-dione, 1-cyclohexyl-3,4-dimethyl-1-phenyl-1H-pyrrole-2,5-dione, 1-cyclohexyl-3-phenyl-1H-pyrrole-2,5-dione, 1-cyclohexyl-3,4-diphenyl-1H-pyrrole-2,5-dione, 2-cyclohexylamino-N-cyclohexylmaleimide and the like.
[0061] Among these monomers, N-methylmaleimide, N-ethylmaleimide, N-isopropylmaleimide, and N-cyclohexylmaleimide are preferred from the viewpoint of excellent weather resistance of methacrylic resins, and N-cyclohexylmaleimide is particularly preferred from the viewpoint of excellent low hygroscopicity required for optical materials in recent years.
[0062] These monomers may be used alone or in combination of two or more.
[0063] In the methacrylic resin of the present embodiment, it is particularly preferable to use the monomer represented by the formula (1) and the monomer represented by the formula (2) in combination, because highly controlled birefringence characteristics can be achieved.
[0064] The molar ratio (X1 / X2) of the content (X1) of the structural unit derived from the monomer represented by formula (1) to the content (X2) of the structural unit derived from the monomer represented by formula (2) is preferably greater than 0 and 15 or less, and more preferably greater than 0 and 10 or less.
[0065] When the molar ratio X1 / X2 is within this range, the molded article including the methacrylic resin of the present embodiment maintains transparency without yellowing, and exhibits good heat resistance and good photoelastic properties without impairing environmental resistance.
[0066] The content of the structural unit (X) derived from the N-substituted maleimide monomer is not particularly limited as long as the resulting composition satisfies the glass transition temperature range of the present embodiment, but is preferably in the range of 5 to 40% by mass, more preferably in the range of 5 to 35% by mass, based on 100% by mass of the methacrylic resin.
[0067] When the content is within this range, the molded body containing the methacrylic resin can obtain a more sufficient improvement effect in heat resistance, and can also obtain a more preferable improvement effect in weather resistance, low water absorption, and optical properties. It should be noted that setting the content of the structural unit (X) derived from the N-substituted maleimide monomer to 40% by mass or less can effectively prevent the reduction in the physical properties of the molded body containing the methacrylic resin due to the reduction in the reactivity of the monomer components during the polymerization reaction and the increase in the amount of the monomer remaining unreacted.
[0068] -Other vinyl monomer units (Y) copolymerizable with the methacrylate monomer-
[0069] Examples of other vinyl monomer units (Y) copolymerizable with the methacrylate monomer (hereinafter sometimes referred to as (Y) monomer units) that can constitute the methacrylic resin of the present embodiment include aromatic vinyl monomer units (Y-1), acrylate monomer units (Y-2), cyanide vinyl monomer units (Y-3), and monomer units (Y-4) other than these.
[0070] The other vinyl monomer units (Y) copolymerizable with the methacrylate monomer may be used alone or in combination of two or more.
[0071] The material of the (Y) monomer unit can be appropriately selected according to the properties required of the methacrylic resin. When properties such as thermal stability, fluidity, mechanical properties, and chemical resistance are particularly required, at least one selected from the group consisting of aromatic vinyl monomer units (Y-1), acrylate monomer units (Y-2), and cyanide vinyl monomer units (Y-3) is preferred.
[0072] [Aromatic vinyl monomer unit (Y-1)]
[0073] The monomer to be the aromatic vinyl monomer unit (Y-1) constituting the methacrylic resin of the present embodiment is not particularly limited, but an aromatic vinyl monomer represented by the following general formula (3) is preferred.
[0074] Chemical formula 3
[0075]
[0076] In the general formula (3), R 13 The group represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms, and the alkyl group may be substituted with, for example, a hydroxyl group.
[0077] R 14 represents any group selected from the group consisting of a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 12 carbon atoms, an aryl group having 6 to 8 carbon atoms, and an aryloxy group having 6 to 8 carbon atoms, and R 14 They can be completely the same groups or different groups. 14 They can also form a ring structure with each other.
[0078] n represents an integer of 0-5.
[0079] Specific examples of the monomer represented by the general formula (3) include, but are not particularly limited to, styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, 2,4-dimethylstyrene, 2,5-dimethylstyrene, 3,4-dimethylstyrene, 3,5-dimethylstyrene, p-ethylstyrene, m-ethylstyrene, o-ethylstyrene, p-tert-butylstyrene, 1-vinylnaphthalene, 2-vinylnaphthalene, 1,1-diphenylethylene, isopropenylbenzene (α-methylstyrene), isopropenyltoluene, isopropenylethylbenzene, isopropenylpropylbenzene, isopropenylbutylbenzene, isopropenylpentylbenzene, isopropenylhexylbenzene, isopropenyloctylbenzene, α-hydroxymethylstyrene, α-hydroxyethylstyrene, and the like.
[0080] Among the above, styrene and isopropenylbenzene are preferred, and styrene is more preferred from the viewpoints of imparting fluidity, improving the polymerization conversion rate, and reducing unreacted monomers.
[0081] In the methacrylic resin of the present embodiment, the above substances can be appropriately selected according to the required properties.
[0082] When heat resistance, reduction of residual monomer types, and balance of fluidity are taken into consideration, the content of the aromatic vinyl monomer unit (Y-1) is preferably 23% by mass or less, more preferably 20% by mass or less, further preferably 18% by mass or less, still further preferably 15% by mass or less, and still further preferably 10% by mass or less, when the total amount of the structural unit derived from the methacrylate monomer and the structural unit (X) is set to 100% by mass.
[0083] When the aromatic vinyl monomer unit (Y-1) is used in combination with the maleimide structural unit (X), the ratio (mass ratio) of the content of the (Y-1) monomer unit to the content of the (X) structural unit (i.e., (Y-1) content / (X) content) is preferably 0.3 to 5 from the viewpoint of processing fluidity during film molding, the effect of reducing silver streaks due to reduction of residual monomers, etc.
[0084] Here, from the viewpoint of maintaining good color tone and heat resistance, the upper limit is preferably 5 or less, more preferably 3 or less, and further preferably 1 or less. From the viewpoint of reducing residual monomers, the lower limit is preferably 0.3 or more, and more preferably 0.4 or more.
[0085] The aromatic vinyl monomer (Y-1) may be used alone or in combination of two or more.
[0086] [Acrylate monomer unit (Y-2)]
[0087] The monomer to be the acrylic acid ester monomer unit (Y-2) constituting the methacrylic resin of the present embodiment is not particularly limited, but an acrylic acid ester monomer represented by the following general formula (4) is preferred.
[0088] Chemical formula 4
[0089]
[0090] In the general formula (4), R 15 represents a hydrogen atom or an alkoxy group having 1 to 12 carbon atoms, R 16 The group represents any one of an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, and an aryl group having 6 to 14 carbon atoms.
[0091] As the monomer for forming the acrylate monomer unit (Y-2), among the methacrylic resins used for the film of the present embodiment, from the viewpoint of improving weather resistance, heat resistance, fluidity and thermal stability, preferred are methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, sec-butyl acrylate, 2-ethylhexyl acrylate, cyclohexyl acrylate, phenyl acrylate and the like, more preferred are methyl acrylate, ethyl acrylate and n-butyl acrylate, and from the viewpoint of ease of acquisition, methyl acrylate and ethyl acrylate are further preferred.
[0092] The acrylic acid ester monomer units (Y-2) may be used alone or in combination of two or more.
[0093] From the viewpoint of heat resistance and thermal stability, when the total amount of the structural unit derived from the methacrylate monomer and the structural unit (X) is 100 mass%, the content of the acrylic acid ester monomer unit (Y-2) when used is preferably 5 mass% or less, more preferably 3 mass% or less.
[0094] [Cyanide vinyl monomer unit (Y-3)]
[0095] The monomer that becomes the vinyl cyanide monomer unit (Y-3) constituting the methacrylic resin of the present embodiment is not particularly limited, and examples thereof include acrylonitrile, methacrylonitrile, ethacrylonitrile, vinylidene cyanide, and the like. Among them, acrylonitrile is preferred from the viewpoint of easy availability and imparting chemical resistance.
[0096] The vinyl cyanide monomer units (Y-3) may be used alone or in combination of two or more.
[0097] From the viewpoint of maintaining solvent resistance and heat resistance, when the total amount of the structural unit derived from the methacrylate monomer and the structural unit (X) is 100 mass%, the content of the vinyl cyanide monomer unit (Y-3) is preferably 15 mass% or less, more preferably 12 mass% or less, and even more preferably 10 mass% or less.
[0098] [Monomer units (Y-4) other than (Y-1) to (Y-3)]
[0099] The monomers that constitute the monomer units (Y-4) other than (Y-1) to (Y-3) constituting the methacrylic resin of the present embodiment are not particularly limited, and examples thereof include amides such as acrylamide and methacrylamide; glycidyl compounds such as (meth)acrylate glycidyl ether and allyl glycidyl ether; unsaturated carboxylic acids such as acrylic acid, methacrylic acid, itaconic acid, maleic acid, and fumaric acid, and their half esters or anhydrides; unsaturated alcohols such as methyl allyl alcohol and allyl alcohol; olefins such as ethylene, propylene, and 4-methyl-1-pentene; vinyl compounds or vinylidene compounds other than the above such as vinyl acetate, 2-hydroxymethyl-1-butene, methyl vinyl ketone, N-vinyl pyrrolidone, and N-vinyl carbazole, and the like.
[0100] Furthermore, examples of crosslinking compounds having a plurality of reactive double bonds include compounds obtained by esterifying both terminal hydroxyl groups of ethylene glycol or its oligomers with acrylic acid or methacrylic acid, such as ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, and tetraethylene glycol di(meth)acrylate; compounds obtained by esterifying the hydroxyl groups of two alcohols with acrylic acid or methacrylic acid, such as neopentyl glycol di(meth)acrylate and di(meth)acrylate; compounds obtained by esterifying polyol derivatives such as trimethylolpropane and pentaerythritol with acrylic acid or methacrylic acid; and polyfunctional monomers such as divinylbenzene.
[0101] Among the monomers constituting the monomer unit (Y), at least one selected from the group consisting of methyl acrylate, ethyl acrylate, styrene, and acrylonitrile is preferred from the viewpoint of availability.
[0102] From the viewpoint of enhancing the effect of imparting heat resistance by the structural unit (X), the content of other vinyl monomer units (Y) copolymerizable with the methacrylate monomer is 0 to 20% by mass, preferably 0 to 18% by mass, and more preferably 0 to 15% by mass, based on 100% by mass of the methacrylic resin.
[0103] In particular, when a cross-linkable polyfunctional (meth)acrylate having a plurality of reactive double bonds is used as the (Y) monomer unit, the content of the (Y) monomer unit is preferably 0.5% by mass or less, more preferably 0.3% by mass or less, and even more preferably 0.2% by mass or less, from the viewpoint of the fluidity of the polymer.
[0104] In particular, in the present embodiment, from the viewpoint of heat resistance and optical properties of the molded article containing the methacrylic resin, when the total amount of the (X) structural unit and the (Y) monomer unit is 100% by mass, the content of the (X) structural unit is 45 to 100% by mass. In this case, the content of the (Y) structural unit is 0 to 55% by mass. Furthermore, the content of the (X) structural unit is preferably 50 to 100% by mass, more preferably 50 to 90% by mass, and even more preferably 50 to 80% by mass.
[0105] The following describes the case where the structural unit (X) derived from the N-substituted maleimide monomer contained in the main chain includes a structural unit derived from N-phenylmaleimide. When the structural unit (X) derived from the N-substituted maleimide monomer contained in the main chain includes a structural unit derived from N-phenylmaleimide, N-phenylmaleimide is used as a raw material.
[0106] The content of the structural unit derived from N-phenylmaleimide is not particularly limited as long as the obtained composition satisfies the glass transition temperature range of the present embodiment, but is preferably in the range of 5 to 40% by mass, more preferably in the range of 5 to 35% by mass, based on 100% by mass of the methacrylic resin.
[0107] When the content is within this range, the molded body containing the methacrylic resin can obtain a more sufficient improvement effect in heat resistance, and can also obtain a more preferable improvement effect in weather resistance, low water absorption, and optical properties. It should be noted that setting the content of the structural unit derived from the N-phenylmaleimide monomer to 40% by mass or less can effectively prevent the reduction in the physical properties of the molded body containing the methacrylic resin due to the reduction in the reactivity of the monomer components during the polymerization reaction and the increase in the amount of the unreacted and residual monomers.
[0108] (N-phenylmaleimide)
[0109] N-substituted maleimide compounds represented by N-phenylmaleimide (phMI) can be manufactured by the following methods: (a) a method of obtaining by a one-step dehydration reaction of maleic anhydride and primary amines; (b) a method of obtaining by a dehydration ring-closing imidization reaction of maleamic acid from maleic anhydride and primary amines; (c) a method of obtaining by a ring-closing imidization reaction of a corresponding maleamic acid monoester, etc., without particular limitation. Among them, the method of (b) is preferred, that is, for example, as a method for manufacturing N-phenylmaleimide, it is particularly preferred to react maleic anhydride and aniline as raw materials to generate N-phenylmaleamic acid (PMA), and subject the N-phenylmaleamic acid to a dehydration ring-closing imidization reaction.
[0110] When N-phenylmaleimide is produced by the method (b) above, aniline and maleic acid are generated by hydrolysis of N-phenylmaleamic acid (PMA) as an intermediate. The generated aniline or aniline from the raw material reacts with N-phenylmaleimide as the target product to generate 2-anilino-N-phenylsuccinimide (APSI) (see the following reaction formula).
[0111] Chemical formula 5
[0112]
[0113] Here, N-phenylmaleimide (phMI) in the present invention refers to a compound having a chemical structure represented by the following formula.
[0114] Chemical formula 6
[0115]
[0116] In addition, N-phenylmaleamic acid (PMA) in the present invention refers to a compound having a chemical structure represented by the following formula.
[0117] Chemical formula 7
[0118]
[0119] In addition, 2-anilino-N-phenylsuccinimide (APSI) in the present invention refers to a compound having a chemical structure represented by the following formula.
[0120] Chemical formula 8
[0121]
[0122] As described above, the intermediate PMA undergoes a dehydration ring-closing imidization reaction to obtain the target product phMI, or undergoes a hydrolysis reaction to generate aniline and maleic acid. Aniline reacts with phMI to produce APSI as a by-product. However, the entire amount is not necessarily completely changed through any reaction, but exists in phMI as an impurity.
[0123] Thus, N-phenylmaleimide (phMI) contains PMA and APSI as impurities. If phMI containing these impurities is used as a component of the comonomer, PMA and APSI are converted into phMI and its analogs through dehydration condensation reaction, oxidation reaction, etc., and therefore, there is a concern that the appearance, heat resistance, strength, etc. of the molded product may be degraded, and it is desired to reduce their content as much as possible.
[0124] The results of the present inventors' research show that by heating the monomers of PMA and APSI at 200°C for 10 minutes, the average gram absorption coefficient of 400-500nm can be confirmed by ultraviolet visible absorption spectrum to increase from 1.6L / (g·cm) to 35.5L / (g·cm) in the case of PMA, and the average gram absorption coefficient of 400-500nm can be confirmed by ultraviolet visible absorption spectrum to increase from 0.02L / (g·cm) to 3.3L / (g·cm) in the case of APSI, and PMA and APSI are decomposed or denatured by heating to components with coloration in the visible light region. In addition, the results of detailed analysis show that one of the components with coloration produced by heating is 2-anilino-N-phenylmaleimide (anilino phMI). That is, in the present invention, it was found that the content of the above-mentioned impurities PMA and APSI affects the quality, especially the coloration, of the copolymer obtained using N-phenylmaleimide.
[0125] The 2-anilino-N-phenylmaleimide (anilino phMI) described in the present invention refers to a compound having a chemical structure represented by the following formula.
[0126] Chemical formula 9
[0127]
[0128] According to the above results, when N-phenylmaleimide is used, it is preferred that PMA is 0.1% by mass or less and APSI is 0.01% by mass or less relative to the total amount of N-phenylmaleimide. That is, when N-phenylmaleimide is used as a monomer, it is preferred to use N-phenylmaleimide (phMI) containing 0.1% by mass or less PMA and 0.01% by mass or less APSI as at least one component of the comonomer.
[0129] The content of PMA in N-phenylmaleimide is preferably 0.1% by mass or less relative to the total amount of N-phenylmaleimide. Here, if N-phenylmaleimide having a content of PMA greater than 0.1% by mass is used as a component of the comonomer, the yellowness YI of the molded body containing the copolymer produced tends to increase, which is not preferred. The detailed mechanism is not clear, but it is speculated that PMA is heated during polymerization and molding, converted to phMI by a dehydration condensation reaction, and a portion of the aniline generated by hydrolysis of PMA reacts with phMI to generate APSI, and then is oxidized during polymerization and molding and converted to a phMI analog, such as anilino phMI, thereby increasing the yellowness YI.
[0130] Relative to the N-phenylmaleimide total amount, the content of the PMA in the N-phenylmaleimide is preferably below 0.1 mass %, more preferably below 0.06 mass %, further preferably below 0.05 mass %, particularly preferably below 0.02 mass %. It should be noted that the lower limit of the content of the PMA in the N-phenylmaleimide is less (that is, 0 mass %) more preferred, from the viewpoint of industry, usually greater than 0 mass %, preferably more than 0.01 mass %.
[0131] In addition, in this specification, the content of PMA is a value which can be measured by the method described in the Examples mentioned later.
[0132] In addition, the content of APSI in N-phenylmaleimide is preferably 0.01% by mass or less relative to the total amount of N-phenylmaleimide. Here, if N-phenylmaleimide having an APSI content of more than 0.01% by mass is used as one component of the comonomer, the yellowness YI of the molded body of the manufactured copolymer tends to increase, which is not preferred. The detailed mechanism is not clear, but it is speculated that not only the coloring of APSI itself, but also the coloring is caused by the oxidation of APSI during polymerization and molding and conversion to phMI analogs, such as aniline phMI.
[0133] Relative to the total amount of N-phenylmaleimide, the content of APSI in N-phenylmaleimide is more preferably 0.008 mass % or less, and further preferably 0.004 mass % or less. It should be noted that the lower limit of the content of APSI in N-phenylmaleimide is more preferably smaller (i.e., 0 mass %), and from an industrial point of view, it is usually greater than 0 mass %, preferably 0.002 mass % or more.
[0134] In addition, in this specification, the content of APSI is a value which can be measured by the method described in the Examples mentioned later.
[0135] (Method for producing N-phenylmaleimide)
[0136] The method for producing N-substituted maleimide compounds represented by N-phenylmaleimide is not particularly limited, and a known method can be used in the same manner or with appropriate modifications. Commercially available N-phenylmaleimide can also be used.
[0137] The N-phenylmaleimide with reduced contents of PMA and APSI as described above can be obtained by the purification method described below. In addition, the above production method is applicable not only to N-phenylmaleimide but also to all N-substituted maleimide compounds.
[0138] The properties of the methacrylic resin according to the present embodiment are described below.
[0139] (Glass transition temperature)
[0140] The glass transition temperature (Tg) of the methacrylic resin of the present embodiment is preferably higher than 120°C and 160°C or lower.
[0141] If the glass transition temperature of the methacrylic resin is higher than 120°C, sufficient heat resistance required for recent optical parts such as lens moldings, automobile parts such as car displays, film moldings for liquid crystal displays, optical films, etc. can be more easily obtained. From the viewpoint of dimensional stability under the temperature conditions of the use environment, the glass transition temperature (Tg) is more preferably 125°C or higher, and further preferably 130°C or higher.
[0142] On the other hand, when the glass transition temperature (Tg) of the methacrylic resin is 160°C or lower, melt processing under extremely high temperature conditions is avoided, thermal decomposition of the resin etc. is suppressed, and a good product can be obtained. For the above reasons, the glass transition temperature (Tg) is preferably 150°C or lower.
[0143] In addition, the glass transition temperature (Tg) can be measured and determined according to JIS-K7121. Specifically, it can be measured using the method described in the examples described later.
[0144] (Weight average molecular weight)
[0145] The methacrylic resin of the present embodiment has a polymethyl methacrylate equivalent weight average molecular weight (Mw) measured by gel permeation chromatography (GPC) of preferably 65,000 to 220,000, more preferably 80,000 to 180,000, and even more preferably 90,000 to 150,000.
[0146] When the weight average molecular weight (Mw) is within the above range, the balance between mechanical strength and fluidity is excellent.
[0147] In addition, regarding the ratio of the Z average molecular weight (Mz), the weight average molecular weight (Mw), and the number average molecular weight (Mn), which are parameters representing the molecular weight distribution, in the methacrylic resin in the present embodiment, considering the balance between fluidity and mechanical strength, Mw / Mn is preferably 1.5 to 3.0, more preferably 1.6 to 2.5, and further preferably 1.6 to 2.3; Mz / Mw is preferably 1.3 to 2.0, more preferably 1.3 to 1.8, and further preferably 1.4 to 1.7.
[0148] In addition, the weight average molecular weight and the number average molecular weight of the methacrylic resin can be measured by the method described in the Examples mentioned later.
[0149] (Method for producing methacrylic resin)
[0150] The method for producing the methacrylic resin according to the present embodiment is described below.
[0151] In the manufacturing method in the present embodiment, as a polymerization form, an intermittent (batch) type, a semi-intermittent (semi-batch) type, and a continuous type can be used. Here, the intermittent type refers to a process in which the total amount of raw materials is put into the reactor to start and continue the reaction, and the product is recovered after the end. In addition, the semi-intermittent type refers to a process in which either the raw material input or the product recovery is carried out simultaneously during the reaction. Further, the continuous type refers to a process in which both the raw material input and the product recovery are carried out simultaneously during the reaction. As a manufacturing method for a methacrylic resin having a structural unit (X) from N-substituted maleimide in the main chain in the present embodiment, from the viewpoint of precisely controlling the composition of the copolymer, a semi-intermittent type in which a part of the raw material input is carried out after the reaction starts is preferably used.
[0152] In the method for producing the methacrylic resin in the present embodiment, it is preferable to use a method for polymerizing the monomer by radical polymerization.
[0153] Hereinafter, the method for producing a methacrylic resin containing a structural unit (X) derived from an N-substituted maleimide will be described in detail.
[0154] As a method for producing the methacrylic resin having a structural unit (X) derived from an N-substituted maleimide monomer in the main chain in the present embodiment, a solution polymerization method is preferred.
[0155] The polymerization solvent used is not particularly limited as long as it increases the solubility of the maleimide copolymer obtained by polymerization and maintains an appropriate viscosity of the reaction solution for the purpose of preventing gelation.
[0156] Specific examples of the polymerization solvent include aromatic hydrocarbons such as toluene, xylene, ethylbenzene, and cumene; ketones such as methyl isobutyl ketone, butyl cellosolve, methyl ethyl ketone, and cyclohexanone; and polar solvents such as dimethylformamide and 2-methylpyrrolidone.
[0157] Furthermore, an alcohol such as methanol, ethanol, or isopropanol may be used in combination as a polymerization solvent within a range that does not inhibit the dissolution of the polymerization product during polymerization.
[0158] These may be used alone or in combination of two or more.
[0159] The amount of solvent during polymerization is not particularly limited as long as it is an amount that allows polymerization, does not cause precipitation of copolymers or monomers used during production, and can be easily removed. For example, when the total amount of the monomers to be formulated is 100 parts by mass, it is preferably 10 to 200 parts by mass, more preferably 25 to 200 parts by mass, further preferably 50 to 200 parts by mass, and further preferably 50 to 150 parts by mass.
[0160] The polymerization temperature is not particularly limited as long as it is a temperature at which polymerization is carried out, but is preferably 70 to 180° C., more preferably 80 to 160° C., further preferably 90 to 150° C., and further preferably 100 to 150° C. From the viewpoint of productivity, it is preferably 70° C. or higher, and in order to suppress side reactions during polymerization and obtain a polymer of a desired molecular weight and quality, it is preferably 180° C. or lower.
[0161] The polymerization time is not particularly limited as long as it is a time that can obtain a desired degree of polymerization at a desired conversion rate, but is preferably 2 to 15 hours, more preferably 3 to 12 hours, and even more preferably 4 to 10 hours from the viewpoint of productivity.
[0162] The polymerization conversion rate of the methacrylic resin having the structural unit (X) derived from the N-substituted maleimide monomer in the main chain at the end of polymerization in the present embodiment is preferably 93 to 99.9%, more preferably 95 to 99.9%, and further preferably 97 to 99.8%.
[0163] Here, the polymerization conversion rate refers to the ratio of the value obtained by subtracting the total mass of the monomers remaining at the end of the polymerization from the total mass of the monomers added to the polymerization system to the total mass of the monomers added to the polymerization system.
[0164] The amount of the N-substituted maleimide monomer remaining in the solution after polymerization (N-substituted maleimide residual amount) is preferably 50 to 5000 mass ppm, more preferably 100 to 3000 mass ppm, and even more preferably 200 to 1000 mass ppm.
[0165] The higher the polymerization conversion rate and the smaller the residual N-substituted maleimide content, the less monomers are returned to the solvent recovery system, so the load on the purification system is reduced. In addition, although the consumption rate (original unit) is increased and economical, if the polymerization conversion rate is too high or the residual N-substituted maleimide content is too low, the amount of low molecular weight components of coloring increases, which may have an adverse effect on color tone and molding processability.
[0166] During the polymerization reaction, a chain transfer agent may be added as necessary to carry out the polymerization.
[0167] As the chain transfer agent, any chain transfer agent used in conventional free radical polymerization can be used, for example, thiol compounds such as n-butyl mercaptan, n-octyl mercaptan, n-decyl mercaptan, n-dodecyl mercaptan, 2-ethylhexyl thioglycolate; halogen compounds such as carbon tetrachloride, dichloromethane, bromoform; unsaturated hydrocarbon compounds such as α-methylstyrene dimer, α-terpinene, dipentene, terpinolene; etc.
[0168] These may be used alone or in combination of two or more.
[0169] These chain transfer agents may be added at any stage without particular limitation as long as the polymerization reaction is in progress.
[0170] The amount of the chain transfer agent added may be 0.01 to 1 part by mass, preferably 0.05 to 0.5 parts by mass, based on 100 parts by mass of the total amount of the monomers used in the polymerization.
[0171] Furthermore, during the polymerization reaction, a polymerization initiator may be added.
[0172] As the polymerization initiator, any initiator generally used in free radical polymerization can be used, for example, organic peroxides such as cumene hydroperoxide, diisopropylbenzene hydroperoxide, di-tert-butyl peroxide, lauroyl peroxide, benzoyl peroxide, tert-butyl peroxyisopropyl carbonate, tert-amyl peroxy-2-ethylhexanoate, tert-amyl peroxyisononanoate, and 1,1-di-tert-butyl peroxycyclohexane; azo compounds such as 2,2'-azobis(isobutyronitrile), 1,1'-azobis(cyclohexanecarbonitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), and dimethyl-2,2'-azobisisobutyrate; etc.
[0173] These may be used alone or in combination of two or more.
[0174] These polymerization initiators may be added at any stage as long as the polymerization reaction is in progress.
[0175] When the total amount of the monomers used in the polymerization is 100 parts by mass, the amount of the polymerization initiator added may be 0.01 to 1 part by mass, and preferably 0.05 to 0.5 parts by mass.
[0176] In solution polymerization, it is important to reduce the dissolved oxygen concentration in the polymerization solution as much as possible. For example, the dissolved oxygen concentration is preferably 10 ppm or less.
[0177] The dissolved oxygen concentration can be measured, for example, using a dissolved oxygen meter DO METER B-505 (manufactured by Iijima Electronics Co., Ltd.). As a method for reducing the dissolved oxygen concentration, a method of bubbling an inert gas into the polymerization solution, a method of repeatedly pressurizing a container containing the polymerization solution to about 0.2 MPa with an inert gas and then releasing the pressure before polymerization, a method of passing an inert gas into a container containing the polymerization solution, and the like can be appropriately selected.
[0178] In order to reduce the difference in the composition of the bound monomers in the copolymers with different molecular weights, it is preferred to polymerize while supplementing the addition of a portion of the monomer units so that the monomer composition in the polymerization system during the polymerization is as uniform as possible. For example, the type, amount and timing of the monomers added in addition are adjusted so that the difference in the consumption rate of each monomer at the moment when about 70% of the total amount of monomers added to the system is consumed is preferably 10% or less, more preferably 5% or less, and further preferably 3% or less. Furthermore, the polymerization is carried out so that the difference in the final conversion rate between the monomers at the end of the polymerization is 10% or less, more preferably 5% or less, and further preferably 3% or less.
[0179] It should be noted that the consumption rate of a certain monomer at a certain moment refers to the proportion of the substance consumed in the polymerization reaction in the total amount of the added monomer, and the total amount of the added monomer also includes the substances that have been added or not added at a certain moment.
[0180] There are no particular limitations on the method for recovering a polymer from a polymer solution obtained by solution polymerization. For example, there may be a method in which, after adding the polymer solution in the presence of an excess of a poor solvent such as a hydrocarbon solvent or an alcohol solvent in which the polymer product obtained by the polymerization is not dissolved, the polymer solution is treated with a homogenizer (emulsification dispersion), and the unreacted monomers are separated from the polymer solution by pre-treatment such as liquid-liquid extraction or solid-liquid extraction; or a method in which the polymerization solvent or unreacted monomers are separated through a process called a devolatilization process and the polymer product is recovered; etc.
[0181] Here, the devolatilization step is a step of removing volatile components such as the polymerization solvent, residual monomers, and reaction by-products under heating and reduced pressure.
[0182] As the apparatus used in the devolatilization process, for example, there can be cited a devolatilization device composed of a tubular heat exchanger and a devolatilization tank; a thin film evaporator such as Wiprene and Exeva manufactured by Kobelco Environmental Solutions, and KONTRO and tilted-wing KONTRO manufactured by Hitachi, Ltd.; an extruder with vents having a residence time and a surface area sufficient to exert devolatilization performance; etc.
[0183] A devolatilization step or the like using a devolatilization device in which two or more of these devices are combined can also be utilized.
[0184] The treatment temperature in the devolatilizer is preferably 150 to 350° C., more preferably 170 to 300° C., and further preferably 200 to 280° C. By setting the temperature at or above the lower limit, residual volatile components can be suppressed, while by setting the temperature at or below the upper limit, coloration and decomposition of the obtained acrylic resin can be suppressed.
[0185] The vacuum degree in the devolatilization device is used in the range of 10 to 500 Torr, preferably in the range of 10 to 300 Torr. By setting the vacuum degree to be below the upper limit, the residual amount of volatile components can be suppressed. In addition, the vacuum degree above the lower limit is realistic in industrial implementation.
[0186] The treatment time is appropriately selected depending on the amount of the residual volatile components, but a shorter treatment time is preferred in order to suppress coloration and decomposition of the obtained acrylic resin.
[0187] The polymer recovered in the devolatilization step may be processed into a pelletized form in a step called a pelletizing step.
[0188] In the pelletizing process, the molten resin can be extruded from a porous die in the form of strands and processed into pellets by cold cutting, hot cutting in the air or underwater cutting.
[0189] In addition, when an extruder with a vent is used as the devolatilization device, the devolatilization step and the granulation step may be combined.
[0190] (Methacrylic resin composition)
[0191] The methacrylic resin composition of the present embodiment includes the methacrylic resin of the present embodiment described above, and the content of 2-amino-N-substituted maleimide in the methacrylic resin composition is less than 0.30 mass ppm. The methacrylic resin composition may optionally include additives in addition to the methacrylic resin of the present embodiment described above, and may include other thermoplastic resins, rubber polymers, etc. other than the methacrylic resin, or may include only the methacrylic resin.
[0192] The content of the methacrylic resin in 100% by mass of the methacrylic resin composition is preferably 50% by mass or more, more preferably 60% by mass or more, further preferably 70% by mass or more, particularly preferably 80% by mass or more.
[0193] -2-Amino-N-substituted maleimide-
[0194] Although all fluorescent coloring components contained in the methacrylic resin composition have not been identified, the present inventors have found that the composition contains 2-amino-N-substituted maleimide produced by the reaction of N-substituted maleimide and primary amine. It is known that 2-amino-N-substituted maleimide itself is a fluorescent coloring component.
[0195] As 2-amino-N-substituted maleimide, for example, when N-phenylmaleimide and N-cyclohexylmaleimide are used as raw materials, 2-anilino-N-phenylmaleimide and 2-cyclohexylamino-N-cyclohexylmaleimide are mainly produced.
[0196] The methacrylic resin composition of the present embodiment has a 2-amino-N-substituted maleimide content in the methacrylic resin reduced to less than 0.30 mass ppm by the production method described later, etc. The content of the 2-amino-N-substituted maleimide is preferably 0 mass ppm or more and less than 0.20 mass ppm, and more preferably 0 mass ppm or more and less than 0.10 mass ppm. Since the methacrylic resin composition of the present embodiment has a 2-amino-N-substituted maleimide content within the above range, it has a good color tone and fluorescent light emission intensity.
[0197] In addition, for the methacrylic resin composition of the present embodiment, it is preferred that the content of 2-amino-N-substituted maleimide relative to the structural unit (X) derived from the N-substituted maleimide monomer in the methacrylic resin (amount of 2-amino-N-substituted maleimide / amount of structural unit (X) derived from the N-substituted maleimide monomer) is reduced to less than 1.5 mass ppm by the manufacturing method described later. The content of 2-amino-N-substituted maleimide relative to the structural unit (X) derived from the N-substituted maleimide monomer is more preferably 0 mass ppm or more and less than 1.0 mass ppm, and further preferably 0 mass ppm or more and less than 0.8 mass ppm. For the methacrylic resin composition of the present embodiment, the content of 2-amino-N-substituted maleimide relative to the structural unit (X) derived from the N-substituted maleimide monomer is within the above range, and therefore, it has good color tone and fluorescent emission intensity.
[0198] The content of 2-amino-N-substituted maleimide in the methacrylic resin composition and the content of 2-amino-N-substituted maleimide relative to the structural unit (X) derived from the N-substituted maleimide monomer can be quantified by the method described in Examples below.
[0199] In addition, the content of 2-amino-N-substituted maleimide in the methacrylic resin composition of this embodiment can be reduced by the method of reducing the content of 2-amino-N-substituted maleimide mentioned later.
[0200] -additive-
[0201] The methacrylic resin composition of the present embodiment may contain various additives within a range not significantly impairing the effects of the present invention.
[0202] The additives are not particularly limited, and examples thereof include antioxidants, light stabilizers such as hindered amine light stabilizers, ultraviolet absorbers, release agents, other thermoplastic resins, paraffin-based processing oils, cycloparaffin-based processing oils, aromatic processing oils, paraffin, organopolysiloxane, softeners and plasticizers such as mineral oils, flame retardants, antistatic agents, inorganic fillers such as organic fibers and pigments such as iron oxide, reinforcing agents such as glass fibers, carbon fibers, and metal whiskers, colorants; organic phosphorus compounds such as phosphites, phosphonites, and phosphates, other additives, or mixtures thereof.
[0203] --Antioxidants--
[0204] The methacrylic resin composition of the present embodiment preferably contains an antioxidant for suppressing deterioration or coloration during molding or use.
[0205] The antioxidant is not limited to the following substances, and examples thereof include hindered phenol antioxidants, phosphorus antioxidants, sulfur antioxidants, etc. The methacrylic resin of the present embodiment can be suitably used for various purposes such as melt extrusion, injection molding, and film molding. The thermal history during processing varies depending on the processing method, and various thermal history is experienced, ranging from tens of seconds like an extruder to tens of minutes to hours like thick-wall molding and sheet molding.
[0206] In the case of a long thermal process, in order to obtain the desired thermal stability, it is necessary to increase the amount of thermal stabilizer added. From the viewpoint of inhibiting the bleeding of the thermal stabilizer and preventing the film from adhering to the roller during film formation, it is preferred to use a plurality of thermal stabilizers in combination, for example, it is preferred to use at least one selected from a phosphorus antioxidant and a sulfur antioxidant in combination with a hindered phenol antioxidant.
[0207] These antioxidants can be used alone or in combination of two or more
[0208] The hindered phenol antioxidant is not limited to the following substances, and examples thereof include pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], diethylene thiobis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 3,3',3",5,5',5"-hexa-tert-butyl-a,a',a"-(mesitylene-2,4,6-triyl)tri-p-cresol, 4,6-bis(octylthiomethyl)-o-cresol, 4,6-bis(dodecylthiomethyl)-o-cresol, ethylenebis(oxyethylene)bis[3-(5-tert-butyl-4-hydroxy-m-tolyl)propionate], hexamethylenebis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 1H,3H,5H)-trione, 1,3,5-tris[(4-tert-butyl-3-hydroxy-2,6-xylyl)methyl]-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 2,6-di-tert-butyl-4-(4,6-bis(octylthio)-1,3,5-triazine-2-ylamine)phenol, 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate, 2-tert-butyl-4-methyl-6-(2-hydroxy-3-tert-butyl-5-methylbenzyl)phenyl acrylate, and the like.
[0209] In particular, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate are preferred.
[0210] In addition, as the hindered phenol antioxidant of the antioxidant, a commercially available phenol antioxidant may be used. Such commercially available phenol antioxidant is not limited to the following substances, and examples thereof include Irganox 1010 (Irganox 1010: pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], manufactured by BASF (BASF)), Irganox 1076 (Irganox 1076: octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, manufactured by BASF (BASF)), Irganox 1330 (Irganox 1330: 3,3',3", 5,5',5"-hexa-tert-butyl-a,a',a"-(mesitylene-2,4,6-triyl)tri-p-cresol, manufactured by BASF (BASF)), and Irganox 3114 (Irganox 3114: 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, manufactured by BASF), Irganox 3125 (Irganox 3125, manufactured by BASF), ADK STAB AO-60 (pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], manufactured by ADEKA), ADK STAB AO-80 (3,9-bis{2-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy]-1,1-dimethylethyl}-2,4,8,10-tetraoxaspiro[5.5]undecane, manufactured by ADEKA), Sumilizer BHT (Sumilizer BHT, manufactured by Sumitomo Chemical Co., Ltd.), Cyanox 1790 (Cyanox 1790, manufactured by SAITEC CO., Ltd.), Sumilizer GA-80 (Sumilizer GA-80, manufactured by Sumitomo Chemical Co., Ltd.), Sumilizer GS (Sumilizer GS: 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate, manufactured by Sumitomo Chemical Co., Ltd.), Sumilizer GM (Sumilizer GM: 2-tert-butyl-4-methyl-6-(2-hydroxy-3-tert-butyl-5-methylbenzyl)phenyl acrylate, manufactured by Sumitomo Chemical Co., Ltd.), vitamin E (manufactured by Eisai Co., Ltd.), and the like.
[0211] Among these commercially available phenolic antioxidants, Irganox 1010, ADK STAB AO-60, ADK STAB AO-80, Irganox 1076, Sumilizer GS, and the like are preferred from the viewpoint of the effect of imparting thermal stability to the resin.
[0212] These may be used alone or in combination of two or more.
[0213] In addition, the phosphorus antioxidant as the antioxidant is not limited to the following substances, and examples thereof include tris(2,4-di-tert-butylphenyl)phosphite, bis(2,4-bis(1,1-dimethylethyl)-6-methylphenyl)ethylphosphite, tetrakis(2,4-di-tert-butylphenyl)(1,1-biphenyl)-4,4'-diylbisphosphite, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, bis(2,6-di-tert-butyl-4 -methylphenyl) pentaerythritol diphosphite, bis(2,4-dicumylphenyl)pentaerythritol-diphosphite, tetrakis(2,4-tert-butylphenyl)(1,1-biphenyl)-4,4'-diylbisphosphite, di-tert-butyl-m-tolyl-phosphite, 4-[3-[(2,4,8,10-tetra-tert-butyldibenzo[d,f][1,3,2]dioxaphosphinocycloheptene)-6-yloxy]propyl]-2-methyl-6-tert-butylphenol, etc.
[0214] Furthermore, a commercially available phosphorus antioxidant may be used as the phosphorus antioxidant. Such commercially available phosphorus antioxidants are not limited to the following substances, and examples thereof include Irgafos 168 (Irgafos 168: tris(2,4-di-tert-butylphenyl)phosphite, manufactured by BASF), Irgafos 12 (Irgafos 12: tris[2-[[2,4,8,10-tetra-tert-butyldibenzo[d,f][1,3,2]dioxaphosphin-6-yl]oxy]ethyl]amine, manufactured by BASF), Irgafos 38 (Irgafos 38: bis(2,4-bis(1,1-dimethylethyl)-6-methylphenyl)ethylphosphite, manufactured by BASF), ADK STAB 329K (ADK STAB-229K, manufactured by ADEKA), ADK STAB PEP-36 (ADK STAB PEP-36, manufactured by ADEKA), ADK STAB PEP-36A (ADK STAB PEP-36A, manufactured by ADEKA), ADK STAB PEP-8 (ADK STAB PEP-8, manufactured by ADEKA), ADK STAB HP-10 (ADK STAB HP-10, manufactured by ADEKA), ADK STAB 2112 (ADK STAB 2112, manufactured by ADEKA), ADK STAB 1178 (ADK STAB 1178, manufactured by ADEKA), ADK STAB 1500 (ADK STAB 1500, manufactured by ADEKA), Sandstab P-EPQ (manufactured by Clariant), Weston 618 (manufactured by General Electric (GE)), Weston 619G (manufactured by General Electric (GE)), Ultranox 626 (manufactured by General Electric (GE)), Sumilizer GP (Sumilizer GP: 4-[3-[(2,4,8,10-tetra-tert-butyldibenzo[d,f][1,3,2]dioxaphosphinylcycloheptene)-6-yloxy]propyl]-2-methyl-6-tert-butylphenol, manufactured by Sumitomo Chemical Co., Ltd.), HCA (9,10-dihydro-9-oxy-10-phosphorylphenanthrene-10-oxide, manufactured by Sanko Co., Ltd.), and the like.
[0215] Among these commercially available phosphorus-based antioxidants, Irgafos 168, ADK STAB PEP-36, ADK STAB PEP-36A, ADK STAB HP-10, and ADK STAB 1178 are preferred, and ADK STAB PEP-36A and ADK STAB PEP-36 are particularly preferred, from the viewpoint of the effect of imparting thermal stability to the resin and the effect of combined use with multiple antioxidants.
[0216] These phosphorus-based antioxidants may be used alone or in combination of two or more.
[0217] The sulfur-based antioxidant as the antioxidant is not limited to the following substances, and examples thereof include 2,4-bis(dodecylthiomethyl)-6-methylphenol (Irganox 1726, manufactured by BASF), 2,4-bis(octylthiomethyl)-6-methylphenol (Irganox 1520L, manufactured by BASF), 2,2-bis{[3-(dodecylmercapto)-1-oxypropoxy]methyl}propane-1,3-diylbis[3-dodecylmercapto]propionate] (ADK STAB AO-412S, manufactured by ADEKA), 2,2-bis{[3-(dodecylmercapto)-1-oxypropoxy]methyl}propane-1,3-diylbis[3-dodecylmercapto]propionate] (KEMINOX PLS, manufactured by CHEMIPROKASEI Co., Ltd.). (manufactured by KAISHA, LTD.), ditridecyl 3,3'-thiodipropionate (AO-503, manufactured by ADEKA), and the like.
[0218] Among these commercially available sulfur antioxidants, ADK STAB AO-412S and KEMINOX PLS are preferred from the viewpoint of the effect of imparting thermal stability to the resin, the effect of combining with a plurality of antioxidants, and the viewpoint of handling properties.
[0219] These sulfur-based antioxidants may be used alone or in combination of two or more.
[0220] The content of the antioxidant may be an amount that can obtain the effect of improving thermal stability. If the content is excessive, there is a concern that bleeding out may occur during processing. Therefore, the content is preferably 5 parts by mass or less, more preferably 3 parts by mass or less, further preferably 1 part by mass or less, further preferably 0.8 part by mass or less, further preferably 0.01 to 0.8 part by mass, and particularly preferably 0.01 to 0.5 part by mass, based on 100 parts by mass of the methacrylic resin.
[0221] There is no particular limitation on the timing of adding the antioxidant, and the following methods may be mentioned: a method of starting polymerization after adding to the monomer solution before polymerization; a method of supplying the antioxidant to the devolatilization step after adding and mixing to the polymer solution after polymerization; a method of granulating the antioxidant after adding and mixing to the molten polymer after devolatilization; and a method of adding and mixing the antioxidant when the pellets after devolatilization and granulation are melt-extruded again. Among them, from the viewpoint of preventing thermal degradation and coloration in the devolatilization step, it is preferred to add the antioxidant after adding and mixing to the polymer solution after polymerization and before the devolatilization step, and then supply the antioxidant to the devolatilization step.
[0222] --Hindered Amine Light Stabilizer--
[0223] The methacrylic resin composition of the present embodiment may contain a hindered amine-based light stabilizer.
[0224] The hindered amine light stabilizer is not particularly limited, but is preferably a compound containing three or more ring structures. Here, the ring structure is preferably at least one selected from the group consisting of an aromatic ring, an aliphatic ring, an aromatic heterocycle and a non-aromatic heterocycle. When a compound has two or more ring structures, the ring structures may be the same or different from each other.
[0225] The hindered amine light stabilizer is not limited to the following substances, and specific examples thereof include bis(1,2,2,6,6-pentamethyl-4-piperidinyl)[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]butyl malonate, a mixture of bis(1,2,2,6,6-pentamethyl-4-piperidinyl)sebacate and methyl 1,2,2,6,6-pentamethyl-4-piperidinyl sebacate, bis(2,2,6,6-tetramethyl-4-piperidinyl)sebacate, 6-(1,1,3,3-tetramethylbutyl)amino-1,3,5-triazine-2,4-diyl}{2,2,6,6-tetramethyl-4-piperidinyl)-1,6-hexanediamine, condensation product of dibutylamine-1,3,5-triazine-N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl-1,6-hexanediamine and N-(2,2,6,6-tetramethyl-4-piperidinyl)butylamine, poly[{6-(1,1,3,3-tetramethylbutyl)amino-1,3,5-triazine-2,4-diyl}{2,2,6,6-tetramethyl yl-4-piperidinyl)imino}hexamethylene{(2,2,6,6-tetramethyl-4-piperidinyl)imino}], tetrakis(1,2,2,6,6-pentamethyl-4-piperidinyl)butane-1,2,3,4-tetracarboxylate, tetrakis(2,2,6,6-tetramethyl-4-piperidinyl)butane-1,2,3,4-tetracarboxylate, 1,2,2,6,6-pentamethyl-4-piperidinyldiol and β,β,β',β'-tetramethyl-2,4,8,10-tetraoxaspiro[5. 5] undecane-3,9-diethanol reaction product, 2,2,6,6-tetramethyl-4-piperidinediol and β,β,β',β'-tetramethyl-2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-diethanol reaction product, bis(1-undecyloxy-2,2,6,6-tetramethylpiperidin-4-yl) carbonate, 1,2,2,6,6-pentamethyl-4-piperidinyl methacrylate, 2,2,6,6-tetramethyl-4-piperidinyl methacrylate, etc.
[0226] Among them, bis(1,2,2,6,6-pentamethyl-4-piperidinyl)[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]butylmalonate containing three or more ring structures, polycondensation products of dibutylamine-1,3,5-triazine-N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl-1,6-hexanediamine and N-(2,2,6,6-tetramethyl-4-piperidinyl)butylamine, poly[{6-(1,1,3,3-tetramethylbutyl)amino-1,3,5-triazine-2,4-diyl}{2 , 2,6,6-tetramethyl-4-piperidinyl)imino}hexamethylene{(2,2,6,6-tetramethyl-4-piperidinyl)imino}], a reaction product of 1,2,2,6,6-pentamethyl-4-piperidinediol and β,β,β',β'-tetramethyl-2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-diethanol, and a reaction product of 2,2,6,6-tetramethyl-4-piperidinediol and β,β,β',β'-tetramethyl-2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-diethanol.
[0227] The content of the hindered amine light stabilizer may be an amount that can obtain the effect of improving the light stability. If the content is excessive, there is a concern that bleeding out may occur during processing. Therefore, the content is preferably 5 parts by mass or less, more preferably 3 parts by mass or less, further preferably 1 part by mass or less, further preferably 0.8 part by mass or less, further preferably 0.01 to 0.8 part by mass, and particularly preferably 0.01 to 0.5 part by mass, based on 100 parts by mass of the methacrylic resin.
[0228] --UV absorber--
[0229] The methacrylic resin composition of the present embodiment may contain a UV absorber.
[0230] There is no particular limitation on the ultraviolet absorber, but preferably an ultraviolet absorber having a maximum absorption wavelength in the range of 280 to 380 nm, for example, benzotriazole compounds, benzotriazine compounds, benzophenone compounds, oxybenzophenone compounds, benzoate compounds, phenol compounds, oxazole compounds, cyanoacrylate compounds, benzoxazinone compounds, etc.
[0231] Examples of the benzotriazole compounds include 2,2′-methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol], 2-(3,5-di-tert-butyl-2-hydroxyphenyl)-5-chlorobenzotriazole, 2-(2H-benzotriazol-2-yl)-p-cresol, 2-(2H-benzotriazol-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol, 2-benzotriazol-2-yl-4,6-di-tert-butylphenol, 2-[5-chloro(2H)-benzotriazol-2-yl]-4-methyl-6-tert-butylphenol, 2-(2H-benzotriazol-2-yl)-4,6-di-tert-butylphenol, 2-(2H-benzotriazol-2-yl)-4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)-4,6-di-tert-butylphenol, and 2-(2H-benzotriazol-2-yl)-4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)-4,6-di-tert-butylphenol. 3,3-tetramethylbutyl)phenol, 2-(2H-benzotriazol-2-yl)-4-methyl-6-(3,4,5,6-tetrahydrophthalimidomethyl)phenol, methyl 3-(3-(2H-benzotriazol-2-yl)-5-tert-butyl-4-hydroxyphenyl)propionate / polyethylene glycol 300 reaction product, 2-(2H-benzotriazol-2-yl)-6-(linear and side chain dodecyl)-4-methylphenol, 2-(5-methyl-2-hydroxyphenyl)benzotriazole, 2-[2-hydroxy-3,5-bis(α,α-dimethylbenzyl)phenyl]-2H-benzotriazole, 3-(2H-benzotriazol-2-yl)-5-(1,1-dimethylethyl)-4-hydroxy-C7-9 side chain and linear alkyl esters.
[0232] Among them, benzotriazole compounds having a molecular weight of 400 or more are preferred. For example, in the case of commercially available products, Kemisorb (registered trademark) 2792 (manufactured by CHEMIPRO KASEI KAISHA, LTD.), ADK STAB (registered trademark) LA31 (manufactured by ADEKA Co., Ltd.), Tinuvin (registered trademark) 234 (manufactured by BASF), etc. are mentioned.
[0233] Examples of the benzotriazine compounds include 2-mono(hydroxyphenyl)-1,3,5-triazine compounds, 2,4-bis(hydroxyphenyl)-1,3,5-triazine compounds, and 2,4,6-tris(hydroxyphenyl)-1,3,5-triazine compounds. Specifically, examples include 2,4-diphenyl-6-(2-hydroxy-4-methoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-ethoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-(2-hydroxy-4-propoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, and 2,4-diphenyl-6-(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine. -1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-hexyloxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-octyloxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-dodecyloxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-benzyloxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-butoxyethoxy)-1,3,5-triazine, 2,4-bis(2-hydroxy-4-butoxyphenyl)-6-(2,4-dibutoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-methoxyphenyl)- )-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-ethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-propoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-hexyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-octyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-dodecyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-benzyloxyphenyl)-1,3,5-triazine 2,4,6-tris(2-hydroxy-4-ethoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-butoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-propoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-methoxycarbonylpropoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-ethoxycarbonylethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-(1-(2-ethoxyhexyloxy)-1-oxopropan-2-yloxy)phenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-propoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-methoxycarbonylpropoxyphenyl)-1,3,5-triazine,6-Tris(2-hydroxy-3-methyl-4-methoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-ethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-propoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-butoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-propoxyphenyl)-1,3,5-triazine, Tris(2-hydroxy-3-methyl-4-butoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-hexyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-octyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-dodec ... Tris(2-hydroxy-3-methyl-4-benzyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-ethoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-butoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-propoxyethoxyphenyl)-1,3,5-triazine triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-methoxycarbonylpropoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-ethoxycarbonylethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-(1-(2-ethoxyhexyloxy)-1-oxopropane-2-yloxy)phenyl)-1,3,5-triazine, etc.
[0234] As the benzotriazine compound, a commercially available product can be used, for example, Kemisorb 102 (manufactured by CHEMIPRO KASEI KAISHA, LTD.), LA-F70 (manufactured by ADEKA Corporation), LA-46 (manufactured by ADEKA Corporation), Tinuvin 405 (manufactured by BASF), Tinuvin 460 (manufactured by BASF), Tinuvin 479 (manufactured by BASF), Tinuvin 1577FF (manufactured by BASF), etc. can be used.
[0235] Among them, from the perspective of high compatibility with acrylic resins and excellent ultraviolet absorption characteristics, it is further preferred to use an ultraviolet absorber having a 2,4-bis(2,4-xylyl)-6-[2-hydroxy-4-(3-alkoxy-2-hydroxypropyloxy)-5-α-cumylphenyl]-s-triazine skeleton ("alkoxy" refers to a long-chain alkoxy group such as octyloxy, nonyloxy, and decyloxy).
[0236] As the ultraviolet absorber, benzotriazole compounds and benzotriazine compounds having a molecular weight of 400 or more are preferred, particularly from the viewpoint of compatibility with the resin and volatility during heating. Furthermore, benzotriazine compounds are particularly preferred from the viewpoint of suppressing decomposition of the ultraviolet absorber itself due to heating during extrusion processing.
[0237] The melting point (Tm) of the ultraviolet absorber is preferably 80° C. or higher, more preferably 100° C. or higher, further preferably 130° C. or higher, and further preferably 160° C. or higher.
[0238] The ultraviolet absorber preferably has a weight loss rate of 50% or less when the temperature is increased from 23°C to 260°C at a rate of 20°C / min, more preferably 30% or less, further preferably 15% or less, further preferably 10% or less, and further preferably 5% or less.
[0239] These ultraviolet absorbers may be used alone or in combination of two or more.
[0240] By using two ultraviolet absorbers having different structures in combination, ultraviolet rays in a wide wavelength range can be absorbed.
[0241] The content of the ultraviolet absorber is not particularly limited as long as it does not hinder heat resistance, moisture and heat resistance, thermal stability and molding processability and is an amount that can exert the effect of the present invention. It is preferably 0.1 to 5 parts by mass, preferably 0.2 to 4 parts by mass or less, more preferably 0.25 to 3 parts by mass, and further preferably 0.3 to 3 parts by mass relative to 100 parts by mass of the methacrylic resin. When the content of the ultraviolet absorber is within this range, the balance of ultraviolet absorption performance, molding properties, etc. is excellent.
[0242] --Release Agent--
[0243] The methacrylic resin composition of the present embodiment may contain a release agent. The release agent is not limited to the following substances, and examples thereof include fatty acid esters, fatty acid amides, fatty acid metal salts, hydrocarbon lubricants, alcohol lubricants, polyalkylene glycols, carboxylates, hydrocarbon paraffin-based mineral oils, and the like.
[0244] The fatty acid ester that can be used as the release agent is not particularly limited, and conventionally known fatty acid esters can be used.
[0245] As fatty acid esters, for example, ester compounds of fatty acids having 12 to 32 carbon atoms such as lauric acid, palmitic acid, margaric acid, stearic acid, oleic acid, arachidic acid, behenic acid and monohydric aliphatic alcohols such as palmityl alcohol, stearyl alcohol, behenyl alcohol, glycerol, pentaerythritol, dipentaerythritol, sorbitan and other polyhydric aliphatic alcohols; complex ester compounds of fatty acids with polybasic organic acids and monohydric aliphatic alcohols or polyhydric aliphatic alcohols, etc. can be used.
[0246] Examples of such fatty acid ester lubricants include cetyl palmitate, butyl stearate, stearyl stearate, stearyl citrate, glyceryl monocaprylate, glyceryl monocaprate, glyceryl monolaurate, glyceryl monopalmitate, glyceryl dipalmitate, glyceryl monostearate, glyceryl distearate, glyceryl tristearate, glyceryl monooleate, glyceryl dioleate, glyceryl trioleate, glyceryl monolinoleate, glyceryl monobehenate, glyceryl mono-12-hydroxystearate, glyceryl di-12-hydroxystearate, glyceryl tri-12-hydroxystearate, glyceryl diacetyl monostearate, glyceryl citric acid fatty acid esters, pentaerythritol adipic acid stearate, montanic acid partially saponified ester, pentaerythritol tetrastearate, dipentaerythritol hexastearate, and sorbitan tristearate.
[0247] These fatty acid ester lubricants may be used alone or in combination of two or more.
[0248] Examples of commercially available products include the RIKEMAL series, POEM series, RIKESTAR series, and RIKEMASTER series manufactured by Riken Vita Co., Ltd., and the EXCEL series, RHEODOL series, EXCEPARL series, and COCONAD series manufactured by Kao Corporation. More specifically, RIKEMAL S-100, RIKEMAL H-100, and POEM RIKEMAL S-200 (リケマールS-200), POEM B-200 (ポエムB-200), RIKESTAR EW-200 (リケスターEW-200), RIKESTAR EW-400(リケスターEW-400), EXCEL S-95(エキセルS-95), RHEODOL MS-50(レオドールMS-50), etc.
[0249] The fatty acid amide-based lubricant is not particularly limited, and a conventionally known lubricant can be used.
[0250] As fatty acid amide lubricants, for example, saturated fatty acid amides such as lauric acid amide, palmitic acid amide, stearic acid amide, behenic acid amide, and hydroxystearic acid amide; unsaturated fatty acid amides such as oleic acid amide, erucic acid amide, and ricinoleic acid amide; substituted amides such as N-stearyl stearic acid amide, N-oleyl oleic acid amide, N-stearyl oleic acid amide, N-oleyl stearic acid amide, N-stearyl erucic acid amide, and N-oleyl palmitic acid amide; hydroxymethyl amides such as hydroxymethyl stearic acid amide and hydroxymethyl behenic acid amide; methylene bis stearic acid amide, ethylene bis capric acid amide, ethylene bis lauric acid amide, and ethylene bis stearic acid amide ( Saturated fatty acid bisamides such as ethylene bisstearylamide), ethylene bisisostearylamide, ethylene bishydroxystearic acid amide, ethylene bisbehenic acid amide, hexamethylene bisstearic acid amide, hexamethylene bisbehenic acid amide, hexamethylene bishydroxystearic acid amide, N,N'-distearyl adipic acid amide, N,N'-distearyl sebacic acid amide; unsaturated fatty acid bisamides such as ethylene bisoleic acid amide, hexamethylene bisoleic acid amide, N,N'-dioleyl adipic acid amide, N,N'-dioleyl sebacic acid amide; aromatic bisamides such as meta-xylylene bisstearic acid amide and N,N'-distearyl isophthalic acid amide, etc.
[0251] These fatty acid amide-based release agents may be used alone or in combination of two or more.
[0252] As commercially available products, for example, DIAMIDO series (manufactured by Nippon Chemical Industry Co., Ltd.), amide series (manufactured by Nippon Chemical Industry Co., Ltd.), Nikka Amide series (manufactured by Nippon Chemical Industry Co., Ltd.), methylolamide series, bisamide series, Suripakkusu series (manufactured by Nippon Chemical Industry Co., Ltd.), Kao wax series (manufactured by Kao Corporation), fatty acid amide series (manufactured by Kao Corporation), ethylene bis stearic acid amides (manufactured by Dainichi Chemical Industries, Ltd.), etc. can be mentioned.
[0253] Fatty acid metal salt refers to a metal salt of a higher fatty acid, and examples thereof include lithium stearate, magnesium stearate, calcium stearate, calcium laurate, calcium ricinoleate, strontium stearate, barium stearate, barium laurate, barium ricinoleate, zinc stearate, zinc laurate, zinc ricinoleate, zinc 2-ethylhexanoate, lead stearate, dibasic lead stearate, lead naphthenate, calcium 12-hydroxystearate, lithium 12-hydroxystearate, and the like. Among them, calcium stearate, magnesium stearate, and zinc stearate are particularly preferred from the viewpoint of making the obtained transparent resin composition excellent in processability and extremely excellent in transparency.
[0254] As an example of commercially available products, there can be mentioned SZ series, SC series, SM series, SA series and the like manufactured by Sakai Chemical Industry Co., Ltd.
[0255] When the fatty acid metal salt is used, the content is preferably 0.2% by mass or less based on 100% by mass of the methacrylic resin composition from the viewpoint of maintaining transparency.
[0256] The above-mentioned release agents may be used alone or in combination of two or more.
[0257] The release agent to be used is preferably one having a decomposition start temperature of 200° C. or higher. The decomposition start temperature can be measured based on the temperature at which 1% of mass is lost in TGA.
[0258] The content of the release agent may be any amount as long as the effect as the release agent can be obtained. However, if the content is excessive, there is a concern that problems such as extrusion failure due to bleeding and screw slippage may occur during processing. Therefore, the content of the release agent is preferably 5 parts by mass or less, more preferably 3 parts by mass or less, further preferably 1 part by mass or less, further preferably 0.8 parts by mass or less, further preferably 0.01 to 0.8 parts by mass, and particularly preferably 0.01 to 0.5 parts by mass, relative to 100 parts by mass of the methacrylic resin. When added in the above range, it is preferred because it suppresses the decrease in transparency caused by the addition of the release agent, and there is also a tendency to suppress poor demolding during injection molding and adhesion to the metal roll during sheet molding.
[0259] --Other thermoplastic resins--
[0260] The methacrylic resin composition of the present embodiment may further contain other thermoplastic resins other than the methacrylic resin for the purpose of adjusting the birefringence and improving flexibility within a range not impairing the purpose of the present invention.
[0261] As other thermoplastic resins, for example, polyacrylates such as polybutyl acrylate; styrene polymers such as polystyrene, styrene-methyl methacrylate copolymer, styrene-butyl acrylate copolymer, styrene-acrylonitrile copolymer, acrylonitrile-butadiene-styrene block copolymer; in addition, for example, 3-4 layer structure acrylic rubber particles described in Japanese Unexamined Patent Publication No. 59-202213, Japanese Unexamined Patent Publication No. 63-27516, Japanese Unexamined Patent Publication No. 51-129449, Japanese Unexamined Patent Publication No. 52-56150, etc.; rubber polymers disclosed in Japanese Unexamined Patent Publication No. 60-17406 and Japanese Unexamined Patent Publication No. 8-245854; methacrylic rubber-containing graft copolymer particles obtained by multi-stage polymerization described in International Publication No. 2014-002491; etc.
[0262] Among them, from the viewpoint of obtaining good optical and mechanical properties, preferred are styrene-acrylonitrile copolymers and rubber-containing graft copolymer particles having a graft portion on the surface layer, wherein the graft portion is composed of a composition that is compatible with a methacrylic resin containing a structural unit (X) derived from an N-substituted maleimide monomer in the main chain.
[0263] The average particle size of the acrylic rubber particles, methacrylic rubber-containing graft copolymer particles, and rubber polymer is preferably 0.03 to 1 μm, more preferably 0.05 to 0.5 μm, from the viewpoint of improving the impact strength and optical properties of a molded body obtained from the composition of this embodiment.
[0264] As content of another thermoplastic resin, when methacrylic resin is 100 parts by mass, it is preferably 0 to 50 parts by mass, and more preferably 0 to 25 parts by mass.
[0265] The glass transition temperature (Tg), weight average molecular weight (Mw), and number average molecular weight (Mn) of the methacrylic resin composition may be the same as those described above with respect to the methacrylic resin.
[0266] (Particles)
[0267] The particles of the present embodiment are composed of a methacrylic resin composition containing a methacrylic resin containing a structural unit (X) derived from an N-substituted maleimide monomer in the main chain.
[0268] The particles of the present embodiment may contain the methacrylic resin of the present embodiment described above, or may be composed of the methacrylic resin composition of the present embodiment described above.
[0269] The content of 2-amino-N-substituted maleimide in the particles of the present embodiment is the same as the content of 2-amino-N-substituted maleimide in the above-mentioned methacrylic resin composition. That is, the content of 2-amino-N-substituted maleimide in the particles is less than 0.30 mass ppm, preferably 0 mass ppm or more and less than 0.20 mass ppm, and more preferably 0 mass ppm or more and less than 0.10 mass ppm. For the particles of the present embodiment, the content of 2-amino-N-substituted maleimide is within the above range, and therefore, has good color tone and fluorescence emission intensity.
[0270] The content of the structural unit (X) derived from the N-substituted maleimide monomer of the methacrylic resin in the particles of the present embodiment (the amount of 2-amino-N-substituted maleimide / the amount of the structural unit (X) derived from the N-substituted maleimide monomer) is the same as the content of the structural unit (X) derived from the N-substituted maleimide monomer of the methacrylic resin in the methacrylic resin composition. That is, the content of the structural unit (X) derived from the N-substituted maleimide monomer of the methacrylic resin in the particles is preferably less than 1.5 mass ppm, more preferably 0 mass ppm or more and less than 1.0 mass ppm, and further preferably 0 mass ppm or more and less than 0.80 mass ppm. The particles of the present embodiment have good color tone and fluorescence emission intensity because the content of the structural unit (X) derived from the 2-amino-N-substituted maleimide monomer in the methacrylic resin is within the above range.
[0271] The content of 2-amino-N-substituted maleimide in the pellets and the content of the structural unit (X) derived from the N-substituted maleimide monomer of the methacrylic resin in the pellets can be quantified by the method described in Examples below.
[0272] In addition, the content of 2-amino-N-substituted maleimide in the particles of the present embodiment can be reduced by the method of reducing the content of 2-amino-N-substituted maleimide described later.
[0273] (Method for producing particles of methacrylic resin composition)
[0274] For the method of manufacturing a methacrylic resin composition, that is, a method of manufacturing particles of a methacrylic resin composition, for example, a method including a kneading step of kneading using a kneading machine such as an extruder, a heating roll, a kneader, a drum mixer, a Banbury mixer, etc. Among them, it is preferred to use an extruder for kneading from the perspective of productivity. The kneading temperature can be set according to the preferred processing temperature of the polymer constituting the methacrylic resin and the other resins mixed, and as a standard, it is in the range of 140 to 300° C., preferably in the range of 180 to 280° C. In addition, in order to reduce the volatile matter, it is preferred to set a vent on the extruder.
[0275] In addition, it is preferred that the method for producing pellets of a methacrylic resin composition includes, as a subsequent step, a light irradiation step as one of the methods for reducing the content of 2-amino-N-substituted maleimide described below.
[0276] The particles of the present embodiment preferably have a reflection tint YI of 10 or less, more preferably 5 or less, and even more preferably 3 or less.
[0277] In addition, the difference ΔYI in the reflective hue YI between the particles of the present embodiment and the particles produced without the means of reducing the content of 2-amino-N-substituted maleimide described later, i.e., the particles having a 2-amino-N-substituted maleimide content of 0.30 mass ppm or more (YI of the particles having a 2-amino-N-substituted maleimide content of 0.30 mass ppm or more - YI of the particles of the present embodiment) is preferably 1 or more, more preferably 3 or more, and further preferably 5 or more.
[0278] The reflectance tint YI value of the particles can be measured by the method described in Examples below.
[0279] Regarding the particles of the present embodiment, the solution YI of the particles is preferably 6 or less, more preferably 5 or less, and even more preferably 4 or less.
[0280] The solution YI value of the particles can be measured by the method described in the examples described later.
[0281] The particles of the present embodiment have excellent transmittance. Preferably, the transmittance of the particles of the present embodiment is improved by 3% or more, more preferably by 6% or more, and further preferably by 9% or more within at least one wavelength range of 1 nm width, relative to the transmittance of particles manufactured without the means for reducing the content of 2-amino-N-substituted maleimide described later, i.e., particles having a content of 2-amino-N-substituted maleimide of 0.30 mass ppm or more. The wavelength at which the transmittance is improved is preferably a low wavelength (e.g., any wavelength of 400 to 460 nm or all wavelengths of 400 to 460 nm).
[0282] The particles of this embodiment can be dissolved in a solvent and the transmittance measured to quantitatively evaluate the effect of improving the color tone due to the reduction in the content of 2-amino-N-substituted maleimide. The average transmittance at a wavelength of 400 nm to 450 nm measured by a cuvette with a 10 cm optical path length for a 20 w / v% chloroform solution of the particles is preferably 90% or more, more preferably 93% or more, and even more preferably 95% or more.
[0283] The transmittance of particles can be measured by the method described in Examples below.
[0284] The fluorescence quantum yield when the fine powder of the particles of this embodiment is excited by light of 400nm wavelength with a half-value width of 5nm is preferably 0.010 or less, more preferably 0.007 or less, and further preferably 0.005 or less. If the fluorescence quantum yield is within the above range, the fluorescence emission is further suppressed, and there is a tendency to form particles with a better color tone.
[0285] Specifically, the fluorescence quantum yield of the particles can be measured by the method described in Examples below.
[0286] (Molding body)
[0287] By molding using the pellets of this embodiment, a molded product including a methacrylic resin composition containing a methacrylic resin having a structural unit (X) derived from an N-substituted maleimide monomer in the main chain and having improved color tone and fluorescence intensity can be obtained.
[0288] Furthermore, it is known that, in particular, when a molded body is obtained by molding the particles of the present embodiment obtained through the light irradiation step, a slightly improved demolding effect is observed during the molding process. The detailed mechanism of the improvement in demolding property is not clear, but it is speculated that by irradiating the particles with light, the reactive bonds such as double bonds and polar functional groups in the coloring source components in the resin become saturated bonds or low-polarity bonds due to some photochemical changes, thereby weakening the interaction with the mold surface, and as a result, the demolding property is improved. In addition, the obtained molded body only improves the color tone and fluorescence intensity, and does not adversely affect the physical properties other than the color tone, such as mechanical properties and thermal properties.
[0289] (Method for producing molded article)
[0290] The method for manufacturing the molded body of the present embodiment includes performing molding using the pellets of the present embodiment. The molding process can use various molding methods such as extrusion molding, injection molding, compression molding, calendaring molding, inflation molding, and hollow molding. Among them, injection molding and injection compression molding are preferably used from the perspective of productivity.
[0291] In general, the injection molding method consists of the following steps: (1) an injection step of melting the resin and filling the cavity of the mold at a controlled temperature with the molten resin; (2) a pressure holding step of applying pressure to the cavity until the gate is sealed and injecting a resin equivalent to the amount of the molten resin filled in the injection step that shrinks after contacting the mold and cooling; (3) a cooling step of releasing the pressure holding and holding the molded body until the resin cools; and (4) a step of opening the mold and taking out the cooled molded body.
[0292] At this time, the molding temperature is in the range of Tg+100° C. to Tg+160° C., preferably Tg+110° C. to Tg+150° C., based on the glass transition temperature of the methacrylic resin composition. Here, the molding temperature refers to the controlled temperature of the tape heater wound around the injection nozzle.
[0293] The mold temperature is in the range of Tg-70°C to Tg, preferably in the range of Tg-50°C to Tg-20°C, based on the glass transition temperature (Tg) of the methacrylic resin composition.
[0294] The injection speed can be appropriately selected according to the thickness and size of the injection-molded body to be obtained, and can be appropriately selected, for example, from the range of 200 to 1000 mm / sec.
[0295] The holding pressure can be appropriately selected according to the shape of the injection molded article to be obtained, and can be appropriately selected within the range of 30 to 120 MPa, for example. When a thin-walled molded article has a fast solidification rate, holding pressure may not be applied.
[0296] Here, the pressure for holding pressure refers to the pressure maintained by the screw for further sending out the molten resin from the gate after the molten resin is filled.
[0297] Injection compression molding refers to an injection molding method that involves slightly opening the mold at the beginning of injection molding, filling the mold with molten resin at high speed and low pressure, and then increasing the mold clamping pressure at high speed to apply a uniform holding pressure to the entire surface of the resin. This allows molding of molded products with excellent surface properties and optical properties.
[0298] When it is desired to obtain an injection-molded article having a thinner thickness, for example, a thickness of less than 1 mm and a diagonal dimension of more than 100 mm, injection compression molding is particularly preferred because a molded article having excellent optical properties and color tone can be obtained.
[0299] In addition, when the injection molded body obtained by using the particles of the above-mentioned methacrylic resin composition is used as a light guide plate, it also includes a substance with fine concavoconvex on its surface. By setting such fine concavoconvex, it is not necessary to set a reflective layer separately by printing, etc., so it is preferred. There is no particular limitation on the fine concavoconvex, and examples include concavoconvex with clear constituent units such as rectangular parallelepiped, cylindrical, elliptical cylinder, triangular prism, spherical, aspherical, etc.; concavoconvex shapes such as pear skin and hairline, and concavoconvex with unclear constituent units or their combination; even concavoconvex with clear constituent units but its shape, especially size, etc. changes. As the shape of the concavoconvex, the height or concave part of the shape can be 0.1μm to 500μm, and the spacing between the concavoconvex can be 10μm to 1000μm.
[0300] Various molded products using the particles of the methacrylic resin and the resin composition thereof according to the present embodiment may be further subjected to surface functionalization treatments such as antireflection treatment, transparent conductive treatment, electromagnetic wave shielding treatment, and gas barrier treatment.
[0301] -Method for reducing the content of 2-amino-N-substituted maleimide (Method for improving the color tone of particles and molded articles of methacrylic resin composition)-
[0302] The present inventors have found that the methacrylic resin composition particles of the present embodiment and a molded article using the particles have improved color tone and fluorescence intensity by reducing 2-amino-N-substituted maleimide, which is one of the fluorescent coloring components contained in the methacrylic resin composition, and have completed the invention.
[0303] It is considered that 2-amino-N-substituted maleimide is generated by the modification of impurities contained in the N-substituted maleimide monomer as a raw material of the methacrylic resin or unreacted N-substituted maleimide remaining after the polymerization step and / or the devolatilization step due to heat, etc. Therefore, as a method for reducing the content of 2-amino-N-substituted maleimide, for example, (1) a method of converting 2-amino-N-substituted maleimide contained in the methacrylic resin composition into other compounds by irradiating particles of the methacrylic resin composition with light, (2) a method of purifying the N-substituted maleimide as a raw material to remove impurities, specifically, a method of removing PMA and APSI which are the sources of 2-amino-N-substituted maleimide, etc. can be used.
[0304] --Shining light to particles--
[0305] The method for producing pellets of a methacrylic resin composition according to the present embodiment preferably includes, as a subsequent step, a step of irradiating pellets of a methacrylic resin composition comprising a methacrylic resin containing a structural unit (X) derived from an N-substituted maleimide monomer in a main chain with light having a wavelength of 360 to 460 nm as a step of reducing the content of 2-amino-N-substituted maleimide.
[0306] The molded body with improved color tone is obtained by molding the pellets irradiated with light according to the present embodiment using the above-mentioned method for producing a molded body.
[0307] The present inventors have found light irradiation conditions that can improve the color tone and fluorescence intensity of the entire pellet in a particularly uniform manner and that do not adversely affect the mechanical and thermal properties of the molded product in the subsequent molding process.
[0308] Although the mechanism is not completely clear, it is assumed that the transmittance (spectral transmittance) of the particles is improved, and the color tone and fluorescence intensity are improved by the mechanism that the coloring component absorbs the irradiated light and turns the coloring component into a non-coloring component. That is, it is speculated that by irradiating the particles with light of a wavelength in the absorption region of the coloring component to cause a photoreaction, the coloring component containing the fluorescent compound is turned into a non-coloring component, and the reflected color tone YI value of the particles, the absorbance in the visible light region, and the fluorescence quantum yield are reduced, thereby making it easy to obtain particles with improved color tone and fluorescence intensity.
[0309] It is believed that in the absorption region, the absorbance in the wavelength range of 360nm to 460nm is also high, and the influence on the YI value is large. Therefore, when irradiating light including a wavelength of 360nm to 460nm, the effect of improving the color tone is high. In fact, the present inventors have studied and found that the content of 2-amino-N-substituted maleimide in the methacrylic resin composition is reduced by irradiating light with a wavelength of 360nm to 460nm. That is, it was confirmed that the 2-amino-N-substituted maleimide as a coloring component absorbs the irradiated light and becomes a non-coloring component.
[0310] As particles that reduce the YI value of the reflected hue (for example, the YI value is reduced by 1 or more) and improve the transmittance by irradiation with light, the above-mentioned particles can be cited. Among them, as described above, by using the methacrylate as the structural unit derived from the methacrylate monomer, setting the content of the structural unit derived from the methacrylate monomer to 50% by mass or more, setting the content of the structural unit (X) to 3-40% by mass, and setting the content of the methacrylic resin to 50% by mass or more, the reflected hue YI value of the particles is more easily reduced and the transmittance is more easily improved by irradiation with light having a wavelength of 360-460 nm.
[0311] The output of the irradiated light is preferably 0.001 to 10 W / cm 2 The light output is less than 0.001W / cm 2 In the case of light output higher than 10W / cm, the photoreaction does not proceed sufficiently and long exposure time is required, so the improvement of color tone may not occur sufficiently. 2 In the case of a part of the absorbed light becoming heat energy and deactivating, the light reaction and the heat reaction lead to the degradation of the resin itself or the generation of new coloring components, so that the reduction of transmittance competes with the improvement of the color tone, and the color tone may be reduced. The above light output is more preferably 0.005 to 5 W / cm 2 , more preferably 0.01 to 3 W / cm 2 The light output of the irradiated light preferably satisfies the above range for the entire particle, and it is more preferred that the irradiation be performed so that the light output is uniform over the entire surface.
[0312] The light output can be measured by a light meter using a photodiode, a power meter, or the like. In addition, by measuring the radiation beam (W), the unit irradiation area (cm 2 The specific light output can be estimated by installing a light meter, a power meter, etc. at a location corresponding to the surface of the particle irradiated with light and measuring the light output.
[0313] In the above-mentioned light irradiation, it is preferred that the light output is constant during the irradiation, but it may also be variable. In the case of varying the light output, there is no problem as long as the light output of the irradiated light is adjusted to satisfy the above-mentioned range. The light may be irradiated from multiple directions or from one direction, but from the viewpoint of uniform irradiation, it is preferred that the light sources are uniformly arranged.
[0314] The cumulative amount of irradiated light is preferably 0.1 W·hr / cm 2 ~10000W·hr / cm 2 When the accumulated light intensity is less than 0.1W·hr / cm 2 In the case of , there is a tendency that the photoreaction does not proceed sufficiently and the improvement of the fluorescence intensity and color tone is insufficient. In addition, when the cumulative light amount is higher than 10000 W·hr / cm 2 In the case of , part of the absorbed light becomes heat energy and is deactivated. The photoreaction and thermal reaction may lead to the degradation of the resin itself or the generation of new coloring components. The reduction in transmittance may compete with the improvement in color tone and lead to a decrease in color tone. The above-mentioned cumulative light intensity is more preferably 0.5W·hr / cm 2 ~5000W·hr / cm 2 , more preferably 1.0 W·hr / cm 2 ~1000W·hr / cm 2 .
[0315] It should be noted that the integrated light quantity can be measured using an integrated light quantity meter using a photodiode, a power meter, etc. In addition, the integrated light quantity is the radiation density (energy density, W / cm 2 ) time (hr) integral value, therefore, if the radiation beam (W) can be measured, then by setting it as unit irradiation area (cm 2 ) to calculate the energy density and the accumulated light intensity based on the irradiation time.
[0316] Regarding the time of irradiation, from the viewpoint of productivity, it is preferred to irradiate for a short time, but if the light irradiation is performed during the storage of the particles, it is also possible to irradiate for a long time. In addition, the light irradiation may be performed continuously or discontinuously, but from the viewpoint of efficiency, it is preferably performed continuously. Preferably, in the case of discontinuous light irradiation, the light output also satisfies the above range.
[0317] The light irradiated to the particles includes light with a wavelength of 360 to 460 nm, preferably mainly includes light with a wavelength of 360 to 460 nm. The light may be light of a single wavelength or light of multiple wavelengths. For example, light including light of a single wavelength or multiple wavelengths within the range of 360 to 460 nm, and light including light of a single wavelength or multiple wavelengths outside the range of 360 to 460 nm, etc. may be cited.
[0318] As for the irradiated light, there is no problem as long as it contains a small amount of light with a wavelength shorter than 360nm. If the molded body is continuously irradiated with light with a short wavelength shorter than 360nm with a high light output for a long time, it will cause decomposition and coloration. Therefore, it is preferred to use only light with a wavelength of 360 to 460nm as the light source. In order to minimize decomposition and coloration, for example, the irradiated light source can be selected so as not to contain light with a wavelength shorter than 360nm, or a filter that filters out wavelengths other than the target wavelength can be combined.
[0319] The irradiated light may include light with a wavelength greater than 460nm. The effect of wavelengths greater than 460nm on the color tone is less with longer wavelengths. However, irradiation with light in the infrared region, in particular, increases the temperature of the particle resin itself. If the temperature increases, the heat may cause the color tone to deteriorate. Therefore, it is preferred to use only light in the visible light region.
[0320] Note that “mainly including light with a wavelength of 360 to 460 nm” means that the spectral output of light with a wavelength of 360 to 460 nm of the light irradiating the particles accounts for 50% or more of the entire irradiated light.
[0321] The temperature of the particles during the light irradiation is preferably within a range of 20° C. or higher and 20° C. or lower than the glass transition temperature of the methacrylic resin composition constituting the particles in order to promote the photoreaction. By irradiating light within the above temperature range, the photoreaction is promoted, and a sufficient color tone improvement effect can be obtained in a shorter time.
[0322] Even if the temperature when irradiating the particles with light is lower than 20°C, the predetermined color tone improvement effect can be obtained. However, if the light is not irradiated for a longer period of time, sufficient color tone improvement may not be expected. On the other hand, if the light irradiation is performed at a temperature higher than 20°C lower than the glass transition temperature, the particles are heated to a temperature above the glass transition region, and the shape of the particles cannot be maintained, and the particles are easily fused with each other.
[0323] For example, when irradiating light including light in the infrared region, the particles can be used without problems as long as the temperature is adjusted to be 20°C lower than the glass transition temperature in consideration of the influence of heating. The effect of improving the color tone can be obtained by using light alone without heating, but it is considered that the effect of improving the color tone can be obtained in a short time by irradiating light while heating to a predetermined degree, which is preferable from the viewpoint of productivity, and the temperature can be appropriately selected in the range of 20°C to 20°C lower than the glass transition temperature of the methacrylic resin composition according to the use situation.
[0324] The temperature is more preferably 30° C. or higher and 25° C. lower than the glass transition temperature of the methacrylic resin composition, and further preferably 40° C. or higher and 30° C. lower than the glass transition temperature.
[0325] In addition, the temperature of the particles can be measured by the method described in the examples described later.
[0326] The light source used in the light irradiation can be appropriately selected from natural light such as sunlight and artificial light sources. Examples of artificial light sources include incandescent lamps, fluorescent lamps, halogen lamps, mercury lamps, metal halide lamps, xenon lamps, LEDs, lasers, etc. Among them, LEDs are preferred from the viewpoint of irradiating only light of a wavelength of 360 to 460 nm, which has a high effect of improving the color tone. The light sources can also be appropriately combined for use in consideration of promoting the reaction by heating, etc.
[0327] When the temperature increase of the particles due to light irradiation becomes a problem, the shape retention and color tone degradation of the particles caused by temperatures above the glass transition region can be suppressed by installing an infrared cut filter or providing a cooling mechanism such as air cooling or water cooling.
[0328] --Purification of N-phenylmaleimide--
[0329] The method for purifying N-phenylmaleimide of the present embodiment can also be obtained by a conventionally known purification method, and is preferably obtained stably and efficiently over a long period of time by repeating the purification steps or making the purification conditions more severe.
[0330] The following describes a preferred embodiment of the method for purifying N-phenylmaleimide, but is not limited to the following. That is, for example, a method in which solid phMI is dissolved in an organic solvent, washed with water below 30°C to remove impurities, and then dried; a method in which solid phMI is dissolved in an organic solvent, washed with an acidic or alkaline aqueous solution, and then dried; a method in which solid phMI is completely dissolved in an organic solvent, filtered with a filter to remove impurities, and then dried the filtrate, etc. can be used. Among them, from the viewpoint of being able to inhibit the hydrolysis of phMI, a method in which solid phMI is completely dissolved in an organic solvent, filtered with a filter to remove impurities, and then dried the filtrate is more preferred.
[0331] The method for purifying N-phenylmaleimide of the present embodiment is preferably a purification method using a filtration step utilizing the difference in solubility between impurities and N-phenylmaleimide in a solvent.
[0332] Here, the organic solvent that can be used when purifying phMI is not particularly limited, but is preferably a water-insoluble or immiscible and inactive (non-reactive) solvent, such as an aromatic compound. Examples of such solvents include benzene, toluene, petroleum fractions having a boiling point of 50 to 120° C., xylene, ethylbenzene, isopropylbenzene, cumene, mesitylene, tert-butylbenzene, methoxybenzene, pseudocumene, trimethylhexane, octane, tetrachloroethane, nonane, chlorobenzene, ethylcyclohexane, petroleum fractions having a boiling point of 120 to 170° C., m-dichlorobenzene, sec-butylbenzene, p-dichlorobenzene, decane, p-cymene, o-dichlorobenzene, butylbenzene, decahydronaphthalene, tetrahydronaphthalene, dodecane, naphthalene, cyclohexylbenzene, and petroleum fractions having a boiling point of 170 to 250° C. The above organic solvents may be used alone or in the form of a mixture of two or more thereof.
[0333] Among the above organic solvents, toluene, o-xylene, m-xylene, and p-xylene are more preferred from the viewpoint of solubility of N-phenylmaleamic acid (PMA) and advantages in filtration efficiency.
[0334] There is no particular restriction on the amount of the organic solvent used, and a solvent is selected that allows smooth filtration and has a large difference in solubility between phMI and PMA and APSI. Furthermore, in consideration of the separation of phMI and the solvent after purification, a low boiling point solvent is sometimes used, and it is more advantageous to purify under pressurized conditions. Here, the concentration of phMI during filtration is not particularly limited as long as it is a concentration at which phMI can be dissolved. Specifically, it is preferred to add 1g to 50g of an organic solvent, more preferably 5g to 30g, and even more preferably 10g to 20g for dissolution, relative to 1g of phMI.
[0335] In addition, the weight ratio of PMA to phMI contained in the mixture of phMI and the organic solvent subjected to the filter filtration is preferably PMA / phMI=6×10 -5 Here, when the weight ratio of PMA to phMI is greater than PMA / phMI=6×10 -5 In the case of , PMA may dissolve too much in the organic solvent and cannot be removed by filtration, and the PMA content in phMI cannot be sufficiently reduced. The weight ratio of PMA to phMI is more preferably PMA / phMI=4×10 -5 The following is particularly preferred: PMA / phMI=3×10 -5 The above weight ratio can be controlled by the temperature of the mixture and the type of solvent.
[0336] PMA / phMI can be calculated, for example, based on the solubility of PMA and phMI under the temperature conditions for filter filtration (filtration temperature) and the amount of phMI and organic solvent used, or it can be determined by measuring the amount of PMA and phMI dissolved in the liquid phase of the organic solvent in which phMI is dissolved by nuclear magnetic resonance (NMR).
[0337] The time for mixing the mixture of phMI and the organic solvent is not particularly limited, but is preferably 5 minutes or more, more preferably 10 minutes or more, and particularly preferably 15 minutes or more from the viewpoint of stabilizing the mass ratio of PMA to phMI (PMA / phMI) and improving the PMA reduction efficiency.
[0338] The temperature for implementing the filter filtration (filtration temperature) is not particularly limited, but from the viewpoint of increasing the difference between the solubility of PMA and APSI and the solubility of phMI, it is preferably 60°C or less, more preferably 40°C or less, further preferably 25°C or less, and particularly preferably 20°C or less.
[0339] The pore size of the filter used for filtration is not particularly limited, but is preferably 1 μm or less, more preferably 0.5 μm or less, and particularly preferably 0.2 μm or less from the viewpoint of the efficiency of the filter in capturing PMA and APSI.
[0340] In order to obtain phMI from the mixture after filtration, the solvent needs to be distilled off, and there is no particular limitation as long as the temperature is lower than the boiling point of phMI. From the viewpoint of inhibiting the decomposition of phMI, it is also preferably 30°C to 100°C, and particularly preferably 50°C to 80°C or less. In addition, the distillation of the solvent can be carried out not only under normal pressure conditions, but also under reduced pressure conditions.
[0341] In addition, the solid phMI remaining after the solvent is distilled off can also be dried under reduced pressure. The temperature during drying is not particularly limited, but is preferably less than the boiling point of phMI. In particular, it is preferably 30°C to 100°C, and in particular, it is more preferably 50°C to 80°C. In addition, the drying of solid phMI can be carried out not only under normal pressure conditions, but also under reduced pressure conditions.
[0342] By the above method, N-phenylmaleimide preferably containing 0.1% by mass or less of N-phenylmaleamic acid (PMA) and preferably containing 0.01% by mass or less of 2-anilino-N-phenylsuccinimide (APSI) can be obtained. As described above, for the N-phenylmaleimide of the present embodiment, the content of these impurities is very small, and therefore, the copolymer obtained by using the N-phenylmaleimide compound has a small content of coloring compounds from impurities that can be generated during polymerization, which can reduce the coloring of the molded body.
[0343] (Application of Molded Article)
[0344] The molded article obtained from the pellets of the present embodiment is a molded article composed of a methacrylic resin composition having low birefringence, excellent heat resistance, and improved transmittance while maintaining transparency, and is therefore suitable for use in applications such as optical parts in household goods, OA equipment, AV equipment, battery electronic equipment parts, lighting equipment, and automobiles.
[0345] As optical components for household items, OA equipment, AV equipment, battery electronic equipment components, lighting equipment, etc., for example, light guide plates, display front panels, and touch screens for displays of smartphones, PDAs, tablet computers, LCD TVs, etc.; further, optical lens components of smartphone and tablet computer camera lenses, head-mounted displays, liquid crystal projectors, etc., for example, prism elements, waveguides, lenses, especially small, thin-walled and unevenly thick optical lenses, optical fibers, optical fiber coating materials, lenses, Fresnel lenses, phase plates with microlens arrays, optical cover components, etc.
[0346] Examples of optical components used in automobiles include light guide plates for in-vehicle displays; in-vehicle instrument panels; optical components for head-up displays such as front panels, combiners, and optical cover components for car navigation systems; and in-vehicle camera lenses and light guide rods.
[0347] In addition to the above, it can also be preferably used for parts of digital signage display devices that circulate information on a thin display connected to a network for the purpose of publicity and advertising in camera focus panels, outdoors, stores, public institutions, transportation institutions, etc.
[0348] Example
[0349] The present invention will be described in detail below with reference to Examples and Comparative Examples. However, the present invention is not limited to the following Examples.
[0350] <1. Determination of impurity content in phMI>
[0351] The phMI used in the Examples and Comparative Examples was dissolved in acetonitrile to prepare a 4 mass % solution, and the solution was measured using the following apparatus and conditions.
[0352] Measurement apparatus: High performance liquid chromatography (LC Ultra3000 LTQ XL, manufactured by Thermo Fisher Scientific).
[0353] The measurement conditions are as follows.
[0354] Chromatographic column: kinetex 2.6XB C-18 5.0×2.1mm.
[0355] Column temperature: 40°C, flow rate: 0.2 mL / min, injection volume: 10 μL.
[0356] Detector: PMA: UV detector (wavelength: 254 nm), APSI: MS (ionization: ESI+, scanning range: m / z=50-1000).
[0357] Mobile phase: A 0.1 mass % formic acid aqueous solution, B 0.1 mass % formic acid acetonitrile solution, and the gradient conditions were as shown in Table 1 below.
[0358] Table 1
[0359]
[0360] <2. Measurement of polymerization conversion rate>
[0361] A portion of the polymerization solution in the examples and comparative examples was collected, and the sample was dissolved in chloroform at the amount of monomers remaining in the polymerization solution sample to prepare a 5 mass % solution, and n-decane was added as an internal standard. The concentration of the monomers remaining in the sample was measured using a gas chromatograph (manufactured by Shimadzu Corporation, GC-2010), and the total mass (a) of the monomers remaining in the polymerization solution was calculated. And, based on the total mass (a), the total mass (b) assuming that all the monomers added until the time of sample collection remain in the polymerization solution, and the total mass (c) of the monomers added until the end of the polymerization step, the polymerization conversion rate (%) was calculated by the calculation formula (ba) / c×100.
[0362] <3. Analysis of structural units>
[0363] pass 1 H-NMR determination and 13 The structural units of the produced methacrylic resin were identified by C-NMR measurement, and the amount thereof was calculated. 1 H-NMR determination and 13 The measurement conditions of C-NMR measurement are as follows.
[0364] Measuring equipment: DPX-400, manufactured by BRUKER, Germany.
[0365] Determination solvent: CDCl3 or DMSO-d6.
[0366] Measurement temperature: 40℃.
[0367] It should be noted that the amount of the structural unit (X) derived from the N-substituted maleimide monomer in the methacrylic resin contained in the pellets is also determined by 1 H-NMR determination and 13The structural unit of the methacrylic resin contained in the particles was identified by C-NMR measurement, and the amount thereof was calculated from the integrated ratio.
[0368] <4. Measurement of molecular weight and molecular weight distribution>
[0369] The weight average molecular weight (Mw) and number average molecular weight (Mn) of the methacrylic resins produced in the Examples and Comparative Examples described below were measured using the following apparatuses and conditions.
[0370] Measuring apparatus: manufactured by Tosoh Corporation, gel permeation chromatography (HLC-8320GPC).
[0371] The measurement conditions are as follows.
[0372] Chromatographic columns: One TSKguardcolumn SuperH-H, two TSKgel SuperHM-M, and one TSKgel SuperH2500 connected in series. Chromatographic column temperature: 40°C.
[0373] The developing solvent was tetrahydrofuran, and the flow rate was 0.6 mL / min. As an internal standard, 0.1 g / L of 2,6-di-tert-butyl-4-methylphenol (BHT) was added.
[0374] Detector: RI (refractive index) detector, detection sensitivity: 3.0 mV / min.
[0375] Sample: 0.02 g of methacrylic acid resin or 20 mL of tetrahydrofuran solution of methacrylic acid resin. Injection volume: 10 μL.
[0376] Standard samples for calibration curve: The following 10 types of polymethyl methacrylates having different molecular weights and known monodisperse weight peak molecular weights (manufactured by Polymer Laboratories; PMMA Calibration Kit MM-10) were used.
[0377] Weight peak molecular weight (Mp)
[0378] Standard reagent 1 1916000 Standard reagent 2 625500 Standard reagent 3 298900 Standard reagent 4 138600 Standard reagent 5 60150 Standard reagent 6 27600 Standard reagent 7 10290 Standard reagent 8 5000 Standard reagent 9 2810 Standard reagent 10 850
[0379] Under the above conditions, the RI detection intensity was measured with respect to the elution time of the methacrylic resin.
[0380] As described above, the weight average molecular weight (Mw) and the number average molecular weight (Mn) of the methacrylic resin were determined based on the calibration curve obtained by measuring the standard sample for calibration curve.
[0381] <5. Glass transition temperature>
[0382] The glass transition temperature (Tg) (° C.) of the methacrylic resin was measured in accordance with JIS-K7121.
[0383] First, the sample was conditioned under a standard condition (23° C., 65% RH) (left at 23° C. for one week), and about 10 mg of the sample was cut out at four points (four places) to prepare test pieces.
[0384] Then, a differential scanning calorimeter (Diamond DSC manufactured by Perkin Elmer Japan) was used under the condition of a nitrogen gas flow rate of 25 mL / min. Here, the temperature was raised from room temperature (23°C) to 200°C at 10°C / min (primary heating), and maintained at 200°C for 5 minutes. After the sample was completely melted, the temperature was lowered from 200°C to 40°C at 10°C / min, and maintained at 40°C for 5 minutes. Further, the temperature was raised again under the above heating conditions (secondary heating). In the DSC curve drawn during this period, the intersection of the curve of the step-shaped change part during the secondary heating and the straight line with the same distance from each baseline extension line in the vertical axis direction (midpoint glass transition temperature) was measured as the glass transition temperature (Tg) (°C). Four points were measured for each sample, and the arithmetic average (rounded off below the decimal point) of the four points was taken as the measured value.
[0385] <6. Measurement of composition distribution of structural units>
[0386] The methacrylic resins obtained in Examples and Comparative Examples were subjected to molecular weight fractionation using the following apparatus and conditions.
[0387] Separation device: LC-908 manufactured by Japan Analytical Industry Co., Ltd.
[0388] The fractionation conditions are as follows.
[0389] Chromatographic column: SHODEX K-2004.
[0390] Eluent: chloroform, flow rate: 3 mL / min.
[0391] Detector: UV detector (254 nm).
[0392] Sample: 3 mass % chloroform solution.
[0393] Fractionation method: inject 3 mL of sample and fractionate at 1-minute intervals with elution time of 18 to 43 minutes.
[0394] The fractionation operation was repeated three times, and the composition ratio of the structural units was determined from the sample selected from the obtained fractions according to the aforementioned <3. Analysis of structural units>. In addition, the molecular weight distribution was measured according to <4. Determination of molecular weight and molecular weight distribution>, and the peak molecular weight (Mp) was determined from the position of the peak apex.
[0395] <7. Quantification of 2-amino-N-substituted maleimide contained in particles>
[0396] The amount of 2-amino-N-substituted maleimide contained in the methacrylic resin composition particles obtained in the examples and comparative examples was quantitatively determined. Specifically, 300 mL of hexane was added to a sample prepared by dissolving 10 g of the methacrylic resin composition particles in chloroform to prepare a 50 mL solution, and the solution-soluble component was reprecipitated, and the solution-soluble component was fractionated and subjected to molecular weight fractionation by fractional GPC under the following measurement conditions.
[0397] Separation device: LC-7080 manufactured by Japan Analytical Industry Co., Ltd.
[0398] The fractionation conditions are as follows.
[0399] Chromatographic column: SHODEX K-2002.5+JAIGEL-2H.
[0400] Eluent: chloroform, flow rate: 3 mL / min.
[0401] Detector: UV detector (254, 400 nm).
[0402] Sample: 3 mass % chloroform solution.
[0403] Fractionation method: inject 3 mL of sample and fractionate at 1-minute intervals with elution time of 18 to 43 minutes.
[0404] Furthermore, the quantitative analysis of the fractions obtained by molecular weight fractionation by GPC was carried out by LC-MS under the following measurement conditions. It should be noted that for the 2-amino-N-substituted maleimide (2-anilino-N-phenylmaleimide, 2-cyclohexylamino-N-cyclohexylmaleimide) generated in the examples and comparative examples, a standard curve was prepared using a substance synthesized according to the synthesis method disclosed in the reference document "Tetrahedron Letters, 2013, 54, 6185-6188." as a standard.
[0405] Measuring apparatus (LC part): Ultimate 3000 manufactured by Thermo Fisher Scientific.
[0406] The measurement conditions are as follows.
[0407] Chromatographic column: Intertsil ODS-3.
[0408] Mobile phase: A = water, B = acetonitrile, flow rate: 3 mL / min.
[0409] Gradient: As shown in Table 2, the mixture of A to B was used as the mobile phase, and the mobile phase was allowed to flow through the column for 35 minutes while switching the composition of the mobile phase at the time shown in the Time (minutes) column.
[0410] Table 2
[0411]
[0412] Column temperature: 40°C.
[0413] Detector: UV detector (254, 400 nm).
[0414] Measurement apparatus (MS part): manufactured by Thermo Fisher Scientific, LTQ XL.
[0415] Ionization: ESI+.
[0416] Sample injection volume: 10 μL.
[0417] The content of 2-amino-N-substituted maleimide quantified by LC-MS, that is, the total content of 2-anilino-N-phenylmaleimide and 2-cyclohexylamino-N-cyclohexylmaleimide was determined.
[0418] <8. Measurement of YI of Particle Color>
[0419] The methacrylic resin composition pellets obtained in Examples and Comparative Examples were used to measure the color tone using a spectrophotometer SD5000 manufactured by Nippon Denshoku Industries Co., Ltd. Specifically, the pellets were filled in a measurement cell attached to the spectrophotometer, and the reflection color tone YI was determined by reflection measurement.
[0420] In addition, according to JIS K7105, the reflection color tone YI is calculated|required from the tristimulus values X, Y, and Z obtained by measurement by the calculation formula of YI=100(1.28X-1.06Z) / Y.
[0421] <9. Measurement of particle transmittance and particle solution YI>
[0422] Using the methacrylic resin composition particles obtained in the examples and comparative examples, the average transmittance of the particles and the YI of the solution of the particles were calculated. Specifically, the methacrylic resin composition particles were made into a 20w / v% chloroform solution (i.e., a solution made in a ratio such that 10g of particles are dissolved in chloroform to form a 50mL solution) as a measurement sample. Using an ultraviolet-visible spectrophotometer (manufactured by Shimadzu Corporation, UV-2600i), a cuvette with a measuring wavelength of 380 to 780nm, a slit width of 2nm, and an optical path length of 10cm, a viewing angle of 10°, an auxiliary light source C, and chloroform as a reference substance, the transmittance was measured, and the average transmittance (%) within the range of a wavelength of 400 to 450nm was calculated.
[0423] In accordance with JIS K7373, the YI of the particle solution was determined from the measured tristimulus values X, Y, and Z using the calculation formula YI=100(1.28X-1.06Z) / Y.
[0424] <10. Fluorescence quantum yield of particles>
[0425] The methacrylic resin composition particles obtained in the examples and comparative examples were crushed to 10 μm or less using a jet mill (manufactured by Aishin Nano Technologies, Nano jetmizer NJ-50-B model) to prepare a measurement sample. The fluorescence quantum yield of the obtained powder was measured using a spectrofluorophotometer (manufactured by Hitachi High-Technologies Corporation, F-7000).
[0426] <11. Production of molded body>
[0427] The methacrylic resin composition pellets obtained in the Examples and Comparative Examples were used to obtain a Figure 1 The strip-shaped piece shown in the figure was injection molded using a strip-shaped mold with a thickness of 4mm×width of 10mm×length of 80mm and a side gate. First, the barrel temperature was set to 270℃, the mold temperature was set to 90℃, and the cooling time was set to 20 seconds or 40 seconds. While changing the injection pressure, the minimum injection pressure (short shot point, SSP) at which the resin completely fills the mold was obtained. Then, the injection pressure was set to SSP+50kgf / cm 2 , injection molding is performed to obtain a long strip-shaped sheet.
[0428] <12. Measurement of color tone of molded article>
[0429] The obtained long-length shaped sheet was measured for spectral transmittance (%) and yellowness YI at a wavelength of 400 to 700 nm under a long-length 80 mm condition using a long-length spectral transmission colorimeter ASA1 manufactured by Nippon Denshoku Industries Co., Ltd. 成型体 As with the hue measurement of the particles, the tristimulus values X, Y, and Z obtained by the measurement are calculated according to YI 成型体 =100(1.28X-1.06Z) / Y to calculate the yellowness YI 成型体 .
[0430] [raw material]
[0431] The raw materials used in the production examples described below are as follows.
[0432] [[monomer]]
[0433] Methyl methacrylate (MMA): manufactured by Asahi Kasei Co., Ltd.
[0434] N-Phenylmaleimide (phMI, hereinafter referred to as “unpurified phMI”): manufactured by Nippon Shokubai Co., Ltd.
[0435] N-Cyclohexylmaleimide (chMI): manufactured by Nippon Shokubai Co., Ltd.
[0436] [[Polymerization initiator]]
[0437] 1,1-Di(tert-butylperoxy)cyclohexane: "Perhexa C" manufactured by NOF Corporation.
[0438] [[Chain transfer agent]]
[0439] n-Octylmercaptan: manufactured by Kao Corporation.
[0440] (Manufacturing of phMI with reduced PMA and APSI content)
[0441] Purified phMI with reduced PMA and APSI contents was produced by the following method.
[0442] -Purification process of N-phenylmaleimide-
[0443] --Production method of purified phMI1--
[0444] 3.5 g of m-xylene (manufactured by Mitsubishi Gas Chemical Co., Ltd., hereinafter referred to as mXy) and 0.30 g of unpurified phMI were weighed and added to a 50 mL screw tube (manufactured by AS ONE CORPORATION, Japan, model: No. 7) with a stirrer (manufactured by AS ONE CORPORATION, Japan, model: C5×15), and stirred at 18° C. for 20 minutes (150 rpm) to dissolve the unpurified phMI in mXy, thereby obtaining a phMI suspension solution. It should be noted that the amount of PMA contained in the unpurified phMI before being dissolved in mXy was 1150 mass ppm, and the amount of APSI was 44 mass ppm.
[0445] Then, the phMI suspension solution was filtered at 60° C. using a 6 mL plastic syringe (manufactured by AS ONE CORPORATION, product number: 2-4031-02) equipped with a polytetrafluoroethylene (PTFE) syringe filter (manufactured by Advantec Toyo Kaisha, Ltd., 13JP020AN, pore size 0.2 μm) to obtain 3.8 g of a solution layer.
[0446] The temperature was raised to 60°C under 4 kPa reduced pressure using an evaporator (manufactured by Tokyo Rikakigi Co., Ltd., model: N-1300E), and the mXy solvent was distilled off from the solution layer. The remaining yellow solid was placed in a dryer (manufactured by AS ONE CORPORATION, Japan, model: AVO-200SB-D) and dried under reduced pressure at 60°C for 2 hours. Finally, 0.29 g of purified phMI yellow solid was obtained. The amount of PMA contained in the purified phMI obtained was 560 mass ppm, and the amount of APSI was 44 mass ppm (hereinafter referred to as purified phMI1).
[0447] --Production Method of Purified phMI2--
[0448] The phMI suspension solution was filtered at 40° C. Purified phMI yellow solid was obtained by the same method as the purified phMI1 under the other conditions. The amount of PMA contained in the obtained purified phMI was 460 mass ppm, and the amount of APSI was 40 mass ppm (hereinafter referred to as purified phMI2).
[0449] --Production Method of Purified phMI3--
[0450] The phMI suspension was filtered at 18° C. Purified phMI yellow solid was obtained by the same method as the purified phMI1 under the other conditions. The amount of PMA contained in the obtained purified phMI was 130 mass ppm, and the amount of APSI was 36 mass ppm (hereinafter referred to as purified phMI3).
[0451] [Comparative Example 1]
[0452] 358.6 kg of methyl methacrylate (MMA), 29.4 kg of the above unpurified phMI, 67.7 kg of N-cyclohexylmaleimide (chMI), 0.77 kg of n-octyl mercaptan as a chain transfer agent, and 224.3 kg of m-xylene (mXy) were weighed and added to a 1.25 m3 / 450 tumbler equipped with a jacketed temperature control device and a stirring blade. 3 The mixture was placed in a reactor and stirred to obtain a mixed monomer solution.
[0453] Then, 88.0 kg of MMA, 6.3 kg of unpurified phMI, and 142.4 kg of mXy were weighed and added to the tank 1 and stirred to obtain a mixed monomer solution for replenishment.
[0454] The internal liquid of the reactor was bubbled with nitrogen at a rate of 30 L / min for 1 hour, and nitrogen was bubbled with nitrogen at a rate of 10 L / min for 30 minutes into the tank 1 to remove dissolved oxygen.
[0455] Then, steam was blown into the jacket to raise the temperature of the solution in the reactor to 115° C., and a polymerization initiator solution prepared by dissolving 0.487 kg of 1,1-di(tert-butylperoxy)cyclohexane in 1.888 kg of mXy was added at a rate of 1.0 kg / hour while stirring at 50 rpm to initiate polymerization.
[0456] It should be noted that during the polymerization, the solution temperature in the reactor was controlled at 115±2° C. by a jacket temperature regulator. 30 minutes after the start of the polymerization, the addition rate of the initiator solution was reduced to 0.5 kg / hour. In addition, from 1 hour to 4 hours after the start of the polymerization, the supplementary mixed monomer solution was added uniformly from tank 1.
[0457] Furthermore, the addition rate of the initiator solution was reduced to 0.25 kg / hour 3.5 hours after the start of the polymerization, and the addition was stopped 5 hours after the start of the polymerization.
[0458] After 12 hours had passed from the start of the polymerization, a polymer solution containing a methacrylic resin having a structural unit (X) derived from an N-substituted maleimide monomer in the main chain was obtained.
[0459] The polymer solution was sampled 2 hours and 12 hours after the start of the polymerization, and the polymerization conversion rate was analyzed based on the residual monomer concentration. The results showed that the polymerization conversion rates after 2 hours were 78.9% for MMA, 77.3% for phMI, and 70.4% for chMI. After 12 hours, the polymerization conversion rates were 97.9% for MMA, 99.4% for phMI, and 99.3% for chMI. Considering the monomers added 2 hours after the start of the polymerization, if the polymerization conversion rates after 2 hours are converted to the consumption rate relative to the total amount of each monomer added until the end of the polymerization, the polymerization conversion rates after 2 hours were 67.2% for MMA, 67.1% for phMI, and 70.4% for chMI.
[0460] The polymer solution was supplied to a concentrator consisting of a tubular heat exchanger and a vaporizer preheated to 250°C and devolatilized. The vacuum degree of the vaporizer was 10 to 15 Torr. The resin flowing down from the vaporizer was discharged by a gear pump, extruded from a wire drawing die, water-cooled, and pelletized to obtain methacrylic resin composition pellets.
[0461] The composition of the obtained particles was confirmed, and the structural units derived from the monomers MMA, phMI, and chMI were 81.0 mass%, 6.6 mass%, and 12.4 mass%, respectively. The weight average molecular weight was 108,000, Mw / Mn was 2.04, and the glass transition temperature was 134°C. In addition, the measurement results of the composition distribution of the structural units are Mp: 253000 (MMA: 81.4 mass%, phMI: 6.5 mass%, chMI: 12.1 mass%), Mp: 176000 (MMA: 81.1 mass%, phMI: 6.6 mass%, chMI: 12.3 mass%), Mp: 111000 (MMA: 80.9 mass%, phMI: 6.7 mass%, chMI: 12.4 mass%), Mp: 88000 (MMA: 80.8 mass%, phMI: 6.7 mass%, chMI: 12.5 mass%), Mp: 48000 (MMA: 80.4 mass%, phMI: 6.8 mass%, chMI: 12.8 mass%).
[0462] The amount of 2-amino-N-substituted maleimide contained in the obtained methacrylic resin composition particles was quantified, and the result was 0.31 mass ppm. The amount of 2-amino-N-substituted maleimide in the particles relative to the structural unit (X) derived from the N-substituted maleimide monomer of the methacrylic resin was 1.6 mass ppm. In addition, the particle color tone was measured using the obtained methacrylic resin composition particles. As a result, the average transmittance in the wavelength range of 400 to 450 nm was 89%, the reflection color tone YI was 6.4 (average value of two measurements), and the solution YI of the particles was 6.2. In addition, the fluorescence quantum yield of the obtained methacrylic resin composition particles was measured, and the fluorescence quantum yield was 0.012.
[0463] In addition, the pellets of Comparative Example 1 were made into the above-mentioned long strip-shaped sheets by injection molding, and the color tone was measured under the condition of long optical path of 80 mm. The results showed that under the molding conditions of cylinder temperature of 270°C, mold temperature of 90°C and cooling time of 20s, the yellowness YI 成型体 The yellowness index YI is 23.7 under the molding conditions of barrel temperature 270℃, mold temperature 90℃ and cooling time 40s. 成型体 It is 24.9.
[0464] [Comparative Example 2]
[0465] Purified phMI was obtained under the same conditions as the purified phMI1 except that the unpurified phMI was dissolved in mXy as N-phenylmaleimide, stirred at 60° C. for 20 minutes (150 rpm), and filtered at 60° C. The amount of PMA contained in the obtained purified phMI was 800 mass ppm, and the amount of APSI was 48 mass ppm (hereinafter referred to as purified phMI4).
[0466] Methacrylic resin composition particles were produced by the same method as in Comparative Example 1 except that purified phMI4 was used.
[0467] [Comparative Example 3]
[0468] APSI was added as N-phenylmaleimide to the purified phMI1 to obtain purified phMI adjusted to an APSI content of 0.03 mass %. The purified phMI thus obtained contained 130 mass ppm of PMA and 3040 mass ppm of APSI (hereinafter referred to as purified phMI5).
[0469] Methacrylic resin composition particles were produced by the same method as in Comparative Example 1 except that purified phMI5 was used.
[0470] (Manufacturing of particles having reduced 2-amino-N-substituted maleimide content)
[0471] The following simple apparatus was prepared for irradiating particles with light.
[0472] -Light irradiation device-
[0473] A plurality of NCSC119BT-V1 (peak emission wavelength 445nm) LED chips manufactured by Nichia Chemical Co., Ltd. are used as blue LEDs and mounted on a substrate as the light source of the light irradiation device. A water-cooled radiator is installed in the device to suppress the heat generated by the light source and the irradiation surface, and a cooler is connected to it so that it has a cooling mechanism. In addition, as an LED driving power supply, a constant current power supply IT6533D manufactured by ITECH is used. The light output of the light irradiation device made by the above-mentioned structure is about 1.25W / cm at a distance of 10mm from the light source under the condition of an applied current of 20A. 2 A jack is installed inside the device so that the distance from the light source can be changed according to the height adjustment. In addition, in order to prevent the irradiated light from directly or indirectly entering the human eye, the device is surrounded by a housing so that the light does not leak to the outside.
[0474] [Example 1]
[0475] As N-phenylmaleimide, purified phMI1 obtained in the purification process of N-phenylmaleimide was used. Methacrylic resin composition particles were obtained by the same method as in Comparative Example 1 under other conditions. The obtained methacrylic resin composition particles were spread on a glass container and irradiated with light for about 1.75 hours by a light irradiation device under the condition of applying an output current of 20A, thereby obtaining light irradiated particles. The cumulative light intensity at this time was 2.2W·hr / cm 2 The distance from the light source to the particle surface was 10 mm. The temperature of the particles during the light irradiation was about 30°C.
[0476] The amount of 2-amino-N-substituted maleimide contained in the obtained methacrylic resin composition particles was quantified, and the result was 0.12 mass ppm. The content of the structural unit (X) derived from the N-substituted maleimide monomer of the methacrylic resin in the particles was 0.63 mass ppm. In addition, the particle color tone was measured using the obtained methacrylic resin composition particles, and the result was that the average transmittance in the range of wavelength 400 to 450 nm was 96%, the reflection color tone YI was 3.7 (average value of two measurements), and the solution YI of the particles was 3.8. In addition, the fluorescence quantum yield of the obtained methacrylic resin composition particles was measured, and the result was that the fluorescence quantum yield was 0.003.
[0477] In addition, the pellets of Example 1 were made into the above-mentioned long strip-shaped sheets by injection molding, and the color tone was measured under the condition of long optical path of 80 mm. The results showed that under the molding conditions of cylinder temperature of 270°C, mold temperature of 90°C and cooling time of 20s, the yellowness YI 成型体 The yellowness index YI is 22.0 under the molding conditions of barrel temperature 270℃, mold temperature 90℃ and cooling time 40s. 成型体 It is 23.9.
[0478] [Example 2]
[0479] As N-phenylmaleimide, unpurified phMI without the purification step of N-phenylmaleimide was used. Methacrylic resin composition particles were prepared by the same method as in Comparative Example 1 under the same conditions as in Example 1, and light irradiated was performed under the same conditions and steps as in Example 1 to obtain light irradiated particles.
[0480] [Example 3]
[0481] As N-phenylmaleimide, purified phMI2 obtained in the purification step of N-phenylmaleimide was used. Methacrylic resin composition particles were prepared by the same method as in Comparative Example 1 under the same conditions as in Example 1, and light irradiated by the same conditions and steps as in Example 1 to obtain light irradiated particles.
[0482] [Example 4]
[0483] As N-phenylmaleimide, purified phMI3 obtained in the purification step of N-phenylmaleimide was used. Methacrylic resin composition particles were prepared by the same method as in Comparative Example 1 under the same conditions as in Example 1, and light irradiated was performed under the same conditions and steps as in Example 1 to obtain light irradiated particles.
[0484] [Example 5]
[0485] A UV-LED lamp (manufactured by Kessil, PR160L-390) was used as a light irradiation device, and the accumulated light intensity was set to 2.2 W·hr / cm 2 The methacrylic resin composition particles obtained in Example 1 were irradiated with light having a wavelength of 390 nm. Except for this, the same conditions and procedures as in Example 1 were used to obtain light-irradiated particles.
[0486] [Example 6]
[0487] A desktop intermittent UV curing device (MUVBA-0.3x0.4x0.5-0038, manufactured by AITEC SYSTEM Co., Ltd.) was used as a light irradiation device, and the accumulated light intensity was 2.2 W·hr / cm 2 The methacrylic resin composition particles obtained in Example 1 were irradiated with light having a wavelength of 365 nm. Except for this, the same conditions and procedures as in Example 1 were used to obtain light-irradiated particles.
[0488] Table 3
[0489]
[0490] (Evaluation of mechanical properties)
[0491] Furthermore, injection-molded sheets according to ASTM standards were obtained from the pellets of the comparative example data and the example data, and their mechanical properties were evaluated by tensile and bending tests. As a result, no differences in mechanical properties were found with or without light irradiation or purification of the raw materials.
[0492] (Evaluation of thermal characteristics)
[0493] For the thermal properties of the particles of the comparative example data and the example data, each particle was heated at a rate of 10°C / min in a nitrogen stream using a TG-DTA apparatus (product name: DTG-60A) and an aluminum krypton cell manufactured by Shimadzu Corporation. The thermal decomposition (TGA) of each particle was measured, and the thermal decomposition start temperature was compared based on the intersection of the tangent lines of the TGA curves. As a result, no difference was found in the thermal decomposition start temperature with or without light irradiation and with or without purification of the raw materials.
[0494] The particles of the methacrylic resin composition of the present embodiment have high heat resistance, and when the particles of the methacrylic resin composition are irradiated with light having a wavelength of 360 to 460 nm, the color tone and fluorescence intensity are improved. In addition, the birefringence of the molded body obtained by (injection) molding the particles of the methacrylic resin composition is highly controlled, and further has a high transmittance. Therefore, the molded body can be suitably used for optical parts such as light guide plates, light guide plates for vehicle-mounted displays, vehicle-mounted instrument panels, and optical parts for head-up displays such as front panels of car navigation systems, combiners, and optical cover parts.
[0495] The pellets and molded articles of the present invention have high heat resistance, highly controlled birefringence, and excellent transparency, and therefore can be suitably used in optical parts for household goods, OA equipment, AV equipment, battery electronic equipment parts, lighting equipment, and automobiles.
[0496] As optical components for household items, OA equipment, AV equipment, battery electronic equipment parts, lighting equipment, etc., for example, light guide plates, display front panels, and touch screens used in displays of smartphones, PDAs, tablet computers, LCD TVs, etc.; further, optical lens components for smartphone and tablet computer camera lenses, head-mounted displays, liquid crystal projectors, etc., for example, prism elements, waveguides, lenses, especially small, thin-walled and unevenly thick optical lenses, optical fibers, optical fiber coating materials, lenses, Fresnel lenses, phase plates with microlens arrays, optical cover components, etc.
[0497] Examples of optical components used in automobiles include light guide plates for in-vehicle displays; in-vehicle instrument panels; optical components for head-up displays such as front panels, combiners, and optical cover components for car navigation systems; and in-vehicle camera lenses and light guide rods.
[0498] In addition to the above, it can also be preferably used for parts of digital signage display devices that circulate information on a thin display connected to a network for the purpose of publicity and advertising in camera focus panels, outdoors, stores, public institutions, transportation institutions, etc.
[0499] In addition, according to the present invention, by improving the color tone and fluorescence intensity of the particles, it is possible to make defective particles that previously exceeded the specifications due to the color tone and fluorescence intensity fall within the range of good particles, which can contribute to the improvement of the yield rate or the expansion of the operating range during manufacturing. Specifically, the increase in the heat residence time during manufacturing promotes the generation of coloring components, resulting in the deterioration of the color tone and fluorescence intensity, and thus has the advantages of, for example, easing the temperature conditions and residence time design in the devolatilization process.
Claims
1. A particle, characterized in that The particles are particles composed of a methacrylic resin composition containing a methacrylic resin, wherein the methacrylic resin contains a structural unit (X) derived from an N-substituted maleimide monomer in the main chain, The particles contain less than 0.30 mass ppm of 2-amino-N-substituted maleimide.
2. The particle according to claim 1, wherein The particles have a reflectance tint YI of 10 or less.
3. The particle according to claim 1 or 2, wherein With respect to a 20 w / v% chloroform solution of the particles, an average transmittance of light having a wavelength of 400 nm to 450 nm measured using a cuvette having an optical path length of 10 cm was 90% or more.
4. The particle according to claim 1 or 2, wherein The fluorescence quantum yield when the fine powder of the particles is excited by light of 400 nm wavelength with a half-value width of 5 nm is 0.010 or less.
5. The particle according to claim 1 or 2, wherein The content of 2-amino-N-substituted maleimide in the particles relative to the structural unit (X) derived from the N-substituted maleimide monomer of the methacrylic resin is less than 1.5 mass ppm, that is, the amount of 2-amino-N-substituted maleimide / the amount of the structural unit (X) derived from the N-substituted maleimide monomer is less than 1.5 mass ppm.
6. The particle according to claim 1 or 2, wherein The methacrylic resin composition contains 50% by mass or more of a methacrylic resin containing a structural unit (X) derived from an N-substituted maleimide monomer in a main chain, assuming that the methacrylic resin composition is 100% by mass.
7. The particle according to claim 1 or 2, wherein The methacrylic resin contains 3% by mass or more of the structural unit (X) derived from the N-substituted maleimide monomer in the main chain, assuming that the methacrylic resin accounts for 100% by mass.
8. A molded body, characterized in that The molded body is obtained by molding the particles according to claim 1 or 2.
9. A method for producing a molded article, which is a method for producing a molded article containing a methacrylic resin composition, characterized in that: The manufacturing method comprises in sequence: A step of obtaining a methacrylic resin by polymerizing a methacrylic acid ester monomer, an N-substituted maleimide monomer, and optionally other vinyl monomers copolymerizable with the methacrylic acid ester monomer, and optionally adding an additive to obtain a methacrylic acid resin composition; The step of forming the methacrylic resin composition into particles; The particles are irradiated with a wavelength of 360 nm to 460 nm and a cumulative light intensity of 0.1 W·hr / cm 2 ~10000W·hr / cm 2 The process of light; The step of heating and melting the particles irradiated with the light to obtain a melt; and A step of injection molding the melt to obtain a molded body.
Citation Information
Patent Citations
Multiilayered polymeric composition
JP1976129449A
Multiilayered polymer compositions
JP1977056150A
Production of impact-resistant acrylic polymer
JP1984202213A
Method for coupling optical waveguide and optical fiber together
JP1985017406A
Highly weather-and impact-resistant acrylic resin granular composite material
JP1988027516A